In-situ control of solid electrolyte interface for improved cycling performance of lithium metal cells

JP2024511168A5Active Publication Date: 2025-03-28SION POWER CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023558793
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-03-24
Publication Date
2025-03-28
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

Lithium metal-based rechargeable batteries using conventional electrolytes suffer from rapid degradation due to the high reactivity of lithium metal with these electrolytes, leading to limited cycle life.

Method used

The formation of a stable solid electrolyte interface (SEI) layer with a higher ratio of fluorine atoms to oxygen atoms adjacent to the electrolyte, containing LiF and Li2CO3, and applying anisotropic forces and high formation voltages during charging and discharging to control the SEI growth, enhancing the compatibility and stability of lithium metal anodes.

Benefits of technology

The SEI layer significantly improves the cycle life and reduces discharge resistance, allowing the batteries to operate efficiently for a larger number of cycles with minimal capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Some aspects of the present invention relate to lithium batteries, and more particularly to in-situ control of the solid electrolyte interface to enhance cycling performance of lithium metal batteries. In some embodiments, an electrochemical cell comprises a solid electrolyte interface (SEI) layer rich in inorganic materials (e.g., LiF, Li2O, Li2CO3) that has various advantageous properties (e.g., improved anode stability, etc.). Some embodiments relate to electrical energy storage methods and methods of using the electrochemical cell. In some cases, the methods include applying an anisotropic force and / or a formation voltage to the cell and forming an inorganic-rich SEI layer in-situ.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to lithium batteries, and more specifically to in-situ control of the solid electrolyte interface to improve the cycling performance of lithium metal batteries. [Background technology]

[0002] In recent years, there has been great interest in developing high energy density rechargeable batteries with lithium-containing anodes. In such cells, current electrolytes, particularly those used for low temperature applications, are typically based on solutions of lithium salts and carbonate electrolytes. In particular, lithium metal-based anodes are highly reactive with typical electrolytes and, as a result, degrade rapidly in the presence of these electrolytes during charging and discharging of the cell. As a result, lithium metal-based rechargeable batteries using such electrolytes generally exhibit limited cycle life. Thus, articles and methods for increasing cycle life and / or other improvements would be beneficial. Summary of the Invention

[0003] The present invention relates generally to lithium batteries, and more specifically to in-situ control of the solid electrolyte interface for improved performance of lithium metal batteries. The subject matter disclosed herein includes, in some cases, interrelated products, alternative solutions to a particular problem, and / or a number of different applications of one or more systems and / or articles.

[0004] In some embodiments, an electrochemical cell is provided.

[0005] In some embodiments, an electrochemical cell includes an anode including a lithium metal, a lithium alloy, or a combination thereof as an anode active material, an electrolyte including a fluorinated organic solvent, a cathode, and a solid electrolyte interphase layer disposed between the anode and the electrolyte, the solid electrolyte interphase layer including an inorganic material including LiF and Li2CO3, and a first ratio of fluorine atoms to oxygen atoms adjacent the electrolyte is higher than a second ratio of fluorine atoms to oxygen atoms adjacent the anode in the solid electrolyte interphase layer.

[0006] In some embodiments, an electrochemical cell includes an anode comprising lithium metal, a lithium alloy, or a combination thereof as an anode active material; an electrolyte comprising a fluorinated organic solvent; a cathode; and a solid electrolyte interfacial layer disposed between the cathode and the electrolyte, the solid electrolyte interfacial layer comprising LiF and having (1) a hardness of 0.001 GPa or more and 5 GPa or less; and / or (2) a porosity of 1% or more and 90% or less; and wherein the electrochemical cell exhibits a decrease in discharge capacity of 10% or less after 100 charge / discharge cycles relative to the discharge capacity at the 5th charge / discharge cycle after formation.

[0007] In some embodiments, an electrochemical cell includes an anode comprising a lithium metal, a lithium alloy, or a combination thereof as an anode active material; an electrolyte comprising a fluorinated organic solvent; a cathode; and a solid electrolyte interfacial layer disposed between the cathode and the electrolyte, the solid electrolyte interfacial layer comprising LiF and having (1) a hardness of 0.001 GPa or more and 5 GPa or less; and / or (2) a porosity of 1% or more and 90% or less; and wherein the electrochemical cell exhibits an increase in discharge resistance of 10% or less after 100 charge / discharge cycles relative to the discharge resistance at the 5th charge / discharge cycle after formation.

[0008] In some embodiments, methods for storing and using electrical energy are provided.

[0009] In some embodiments, a method includes performing, in an electrochemical cell including: an anode comprising lithium metal, a lithium alloy, or a combination thereof as an anode active material, the anode having a surface; a cathode; and an electrolyte comprising a fluorinated organic solvent disposed between the cathode and the anode; applying an anisotropic force to a surface of the anode; applying a formation voltage during at least one period during charging and / or discharging of the cell; and forming a solid electrolyte interfacial layer adjacent to the surface of the anode, the formation voltage being greater than 4.35 V; and the solid electrolyte interfacial layer comprising an inorganic material comprising LiF and Li2CO3. [Brief description of the drawings]

[0010] Non-limiting embodiments of the present invention will now be described, by way of example, with reference to the accompanying drawings, which are schematic and are not intended to be drawn to scale, in which each identical or nearly identical component shown is typically represented by a single numeral, and for the sake of clarity, not every component is necessarily labeled in every figure, nor are the figures necessarily all components of each embodiment of the present invention shown, unless necessary to enable a person skilled in the art to understand the invention. [Figure 1] FIG. 1 is a cross-sectional schematic diagram of an electrochemical cell including a solid electrolyte interface (SEI) layer, according to various embodiments. [Diagram 2] 1 is a cross-sectional schematic diagram of a solid electrolyte interfacial layer comprising LiF, according to some embodiments. [Figure 3A] 1 is a cross-sectional schematic diagram of a solid electrolyte interface (SEI) layer including a substantially non-uniform distribution of inorganic material (e.g., LiF and / or Li2CO3), according to various embodiments. [Figure 3B] FIG. 2 is a cross-sectional schematic diagram of a solid electrolyte interface (SEI) layer including a substantially homogeneous distribution of inorganic material (e.g., LiF and / or Li2CO3), according to various embodiments. [Figure 4]1 is a graph showing a comparison of cell cycle life of an electrochemical cell including a LiF-rich SEI layer and cycled with and without pressure, according to some embodiments. [Diagram 5] 1 is a graph showing a comparison of cell cycle life of an electrochemical cell including a LiF-rich SEI layer and cycled with and without pressure, according to some embodiments. [Figure 6] 1 is a graph showing a comparison of cell cycle life of an electrochemical cell including a LiF-rich SEI layer and cycled with and without pressure, according to some embodiments. [Figure 7] 1 is a graph showing a comparison of cell cycle life of an electrochemical cell including a LiF-rich SEI layer and cycled with and without pressure, according to some embodiments. [Figure 8A] 1 is a graph showing a comparison of cell cycle life of an electrochemical cell including a LiF-rich SEI layer and cycled with and without pressure, according to some embodiments. [Figure 8B] 8B is a graph showing the 5 minute discharge resistance of the electrochemical cell from FIG. 8A, according to some embodiments. [Figure 9] 1 is a graph illustrating a comparison of cell cycle life of an electrochemical cell having a LiF-rich SEI layer to an electrochemical cell without a LiF-containing SEI layer, according to some embodiments. [Figure 10] 1 is a graph illustrating a comparison of cell cycle life of an electrochemical cell with no applied pressure and a LiF-rich SEI layer to an electrochemical cell without applied pressure and a LiF-rich SEI layer, according to some embodiments. [Figure 11]1 is a graph illustrating a comparison of the cell cycle life of an electrochemical cell with applied pressure and a LiF-rich SEI layer to an electrochemical cell without applied pressure and a LiF-rich SEI layer, according to some embodiments. [Figure 12A] 1 is a graph showing cell cycle life of electrochemical cells including inorganic-rich SEI layers formed at different formation voltages, according to some embodiments. [Figure 12B] 12B is a graph showing the 5 minute discharge resistance of the electrochemical cell of FIG. 12A, according to some embodiments. [Figure 13] 1 is a graph showing cell cycle life for electrochemical cells cycled at various formation voltages in the presence of LiBOB, according to some embodiments. [Figure 14] 1 is a graph showing cell cycle life for electrochemical cells including relatively high fluoroethylene carbonate (FEC) content and cycled at various formation voltages, according to some embodiments. [Figure 15] 1 is a graph showing cell cycle life for electrochemical cells containing high fluoroethylene carbonate (FEC) content and LiBOB and cycled at various formation voltages, according to some embodiments. [Figure 16] 1 is a graph showing cell cycle life for electrochemical cells including acetate-based solvents cycled at various formation voltages at room temperature, according to some embodiments. [Figure 17] 1 is a graph showing cell cycle life of electrochemical cells including acetate-based solvents cycled at various formation voltages at 0° C., according to some embodiments. [Figure 18] 1 is a graph showing a comparison of cell cycle life of an electrochemical cell including LiFSI and cycled with and without pressure, according to some embodiments. [Figure 19]1 is a graph showing a comparison of cell cycle life of electrochemical cells including LiFSI cycled with and without pressure in the presence of higher amounts of fluoroethylene carbonate (FEC), according to some embodiments. [Figure 20A] 1 is a SEM image of a 50 μm scale bar of an SEI layer formed between an anode and a separator according to some embodiments. [Figure 20B] 20B is an EDS mapping of the SEI layer from FIG. 20A according to some embodiments. [Figure 20C] FIG. 20B is a high magnification SEM image of a 500 nm scale bar of the SEI layer adjacent to the separator from FIG. 20A according to some embodiments. [Figure 21] 1 is a SEM / EDS line scan image of a 5 μm scale bar of an SEI layer according to some embodiments. [Figure 22A] 1 is an X-ray photoelectron spectroscopy (XPS) graph of fluorine content (F 1s) in the SEI layer according to some embodiments. [Figure 22B] 1 is an XPS graph of lithium content (Li 1s) in the SEI layer, according to some embodiments. [Figure 22C] 1 is an XPS graph of carbon content (C 1s) in the SEI layer, according to some embodiments. [Diagram 23] 1 is an X-ray diffraction (XRD) spectrum characterizing the crystallinity of an SEI layer according to some embodiments. [Figure 24] FIG. 1 shows a comparison of the cycling performance of an electrochemical cell cycled with and without pressure, according to some embodiments. [Diagram 25] 1 is a SEM / EDS line scan of an electrochemical cell that was cycled without fluorinated solvents and without applied pressure, according to some embodiments. [Figure 26]1 is a SEM / EDS line scan of an electrochemical cell that does not contain fluorinated solvents and has been cycled under pressure, according to some embodiments. [Figure 27] 1 is a SEM / EDS line scan of an electrochemical cell containing a fluorinated solvent and cycled without applied pressure, according to some embodiments. [Figure 28] 1 is a SEM / EDS line scan of an electrochemical cell containing a fluorinated solvent and cycled under pressure, according to some embodiments. [Figure 29] 1 is a graph showing the percent (%) of remaining Li for cells cycled under pressure with and without fluorinated solvents, according to some embodiments. [Diagram 30] 1 is a graph showing discharge capacity as a function of cycles for cells cycled under pressure with and without fluorinated solvents, according to some embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Some aspects of the present invention relate to electrochemical cells for lithium batteries. In some embodiments, the electrochemical cell comprises a stable solid electrolyte interface (SEI) layer formed at the interface between the anode and the electrolyte, for example, as a result of an interaction (e.g., reaction) between the anode and the electrolyte. The solid electrolyte interface layer may advantageously contain a substantial amount of a particular inorganic material that improves the performance of the electrochemical cell, such as LiF and / or Li2CO3. For example, the solid electrolyte interface layer can help improve the stability of the anode during cycling (or reduce the degradation of the anode), improve the compatibility between a typical electrolyte and a lithium metal anode, and / or improve the cycle life of the cell.

[0012] Some aspects of the present invention relate to methods of forming and using electrochemical cells that include certain inorganic-rich stable SEI layers. For example, application of anisotropic forces and / or high formation voltages to the electrochemical cell during charging and discharging can lead to the in-situ formation of inorganic-rich, controlled SEI layers that improve overall cell performance. For example, the cells can exhibit improved performance, such as slower growth of discharge resistance, controlled SEI growth, reduced cell polarization during charging and discharging, longer cycle life, and / or improved low temperature performance.

[0013] In some embodiments, an electrochemical cell is provided herein. In some such embodiments, the electrochemical cell comprises a first electrode (e.g., an anode), an electrolyte comprising a fluorinated organic solvent, a second electrode (e.g., a cathode), and a solid electrolyte interface layer disposed between the first electrode (e.g., anode) and the electrolyte. For example, FIG. 1 illustrates such an embodiment. As illustrated, the electrochemical cell 10 comprises an anode 12, an electrolyte 14, a cathode 16, and a solid electrolyte interface layer 18 disposed between the anode 12 and the electrolyte 14. In some embodiments, the electrochemical cell includes a porous separator material that may include a non-solid electrolyte. For example, the electrolyte 14 may be impregnated into the porous separator. As used herein, a non-solid electrolyte may refer to a material that cannot withstand static shear stress and where the non-solid experiences a continuous and permanent distortion when shear stress is applied. Examples of non-solids include, for example, liquids, deformable gels, and the like.

[0014] In some embodiments where a separator is present, the separator may be disposed between a first electrode (e.g., an anode) and a second electrode (e.g., a cathode) and includes pores in which an electrolyte can reside. In some such embodiments, a solid electrolyte interfacial layer is disposed between the first electrode (e.g., an anode) and the separator, which includes pores filled with the electrolyte. In some embodiments, the anode includes lithium metal, a lithium alloy, or a combination thereof as an anode active material. Anode active material refers to any electrochemically active species associated with the anode.

[0015] In some embodiments, the solid electrolyte interface layer includes one or more inorganic materials that can advantageously increase the stability of the anode, thereby increasing the cycle life of the electrochemical cell. Non-limiting examples of such inorganic materials include, but are not limited to, LiF, Li2CO3, Li2O, and the like. In some such embodiments, the formation of the one or more inorganic materials in the solid electrolyte interface layer may result from decomposition of the electrolyte and / or interaction of the electrolyte with the anode active material, as described in more detail below.

[0016] In some embodiments, the solid electrolyte interface layer comprises LiF. FIG. 2 is a schematic cross-sectional view of a portion 100 of an electrochemical cell (e.g., electrochemical cell 10 of FIG. 1) including a solid electrolyte interface layer comprising LiF, according to some embodiments. As shown, a solid electrolyte interface layer 18 comprising LiF having a thickness 19 is disposed between a portion of the anode 12 and a portion of the electrolyte 14. In some embodiments, the solid electrolyte interface layer is LiF-rich, e.g., LiF is present in a relatively high loading in the solid electrolyte interface layer and / or is present in a relatively high loading compared to other inorganic materials in the solid electrolyte interface layer. It should be noted that although only LiF is shown in FIG. 2, other inorganic materials (e.g., Li2O) may also be present in the solid electrolyte interface layer, as described in more detail below.

[0017] In some embodiments, the electrochemical cell may be a lithium-based electrochemical cell, such as a lithium-sulfur electrochemical cell, a lithium ion electrochemical cell, a lithium metal lithium ion electrochemical cell, an intercalated lithium metal oxide electrochemical cell, or an intercalated lithium metal phosphate electrochemical cell.

[0018] In some embodiments, the solid electrolyte interface layer includes inorganic materials including LiF and Li2CO3. FIG. 3A is a schematic cross-sectional view of a portion 200 of an electrochemical cell (e.g., electrochemical cell 10 of FIG. 1) including a solid electrolyte interface layer including LiF and Li2CO3 according to some embodiments. As shown in FIG. 3A, a solid electrolyte interface layer 118 including mixed LiF and Li2CO3 is disposed between a portion of the anode 12 and a portion of the electrolyte 14. In some embodiments, the solid electrolyte interface layer may be both LiF-rich and Li2CO3-rich, e.g., each of LiF and Li2CO3 is present in a relatively high loading in the solid electrolyte interface layer and / or is present in a relatively high loading compared to the presence of certain other inorganic materials in the solid electrolyte interface layer. The inorganic materials (e.g., LiF, Li2CO3) may be present in any of the various amounts described herein. In some aspects, the solid electrolyte interface layer may further include one or more inorganic materials, such as, but not limited to, lithium alkoxides, lithium oxides, lithium salts, and other decomposition products of the electrolyte.

[0019] In some embodiments, the solid electrolyte interface layer includes a substantially non-uniform distribution of various inorganic materials and / or atomic species. For example, in one set of embodiments, a first ratio of fluorine atoms to oxygen atoms adjacent to the electrolyte (or facing an electrode, such as an anode) in the solid electrolyte interface layer is higher than a second ratio of fluorine atoms to oxygen atoms adjacent to an electrode (e.g., an anode). Referring again to FIG. 3A, the Li2CO3 and LiF species in the solid electrolyte interface layer 118 are not substantially uniformly distributed within the solid electrolyte interface layer 118 across the thickness 119 of the solid electrolyte interface layer 118. Rather, in FIG. 3A, a substantially higher loading of LiF species is localized at or near the surface of the solid electrolyte interface layer adjacent to the electrolyte 14. Thus, across the thickness 119 of the solid electrolyte interface layer, a first ratio of fluorine atoms to oxygen atoms adjacent to the electrolyte 14 in the solid electrolyte interface layer 118 is higher than a second ratio of fluorine atoms to oxygen atoms adjacent to the anode 12. It should be understood that in addition to LiF and Li2CO3, in some cases, additional inorganic materials (e.g., Li2O, lithium alkoxides, etc.) may also be present and contribute to the ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. For example, in some embodiments, the solid electrolyte interface layer may include a relatively small amount of fluorine-containing inorganic material associated with the presence of a fluorine-containing salt and / or additive (e.g., LixPFy, LixPOyFz, etc.).

[0020] In some embodiments in which the fluorine and oxygen atoms are not substantially uniformly distributed across the thickness of the solid electrolyte interface layer, the ratio of fluorine atoms to oxygen atoms (fluorine / oxygen) at any given point within a cross-section of the thickness of the solid electrolyte interface layer changes by at least 25% (e.g., at least 30%, at least 50%, at least 70%, or at least 90%, etc.) compared to the average ratio of fluorine atoms to oxygen atoms throughout the solid electrolyte interface layer. For example, referring again to FIG. 3A , a first ratio of fluorine atoms to oxygen atoms at any point A (e.g., a point adjacent to the electrolyte) or a second ratio of fluorine atoms to oxygen atoms at any point B (e.g., a point adjacent to the anode) of the cross-section 121 of the solid electrolyte interface layer 118 changes by at least 25% compared to the average ratio of fluorine atoms to oxygen atoms throughout the solid electrolyte interface layer 118. As an exemplary calculation, if a solid electrolyte interface layer has an average ratio of fluorine atoms to oxygen atoms of 1, and any point in a cross section across the thickness of the solid electrolyte layer (e.g., points A or B in FIG. 3B ) has a ratio of 0.75 or less or 1.25 or more, the solid electrolyte interface layer is considered to be substantially inactive; if point A or B in FIG. 3B ) has a ratio of 0.75 or less or 1.25 or more, the solid electrolyte interface layer is considered to have a substantially non-uniform distribution of fluorine atoms and oxygen atoms across the thickness of the solid electrolyte interface layer based on the average ratio of fluorine atoms and oxygen atoms in the solid electrolyte interface layer.

[0021] In some embodiments, a first ratio of fluorine atoms to oxygen atoms on one side of the solid electrolyte interface layer (e.g., adjacent to the electrolyte) is higher than a second ratio of fluorine atoms to oxygen atoms on another side of the solid electrolyte interface layer (e.g., adjacent to the anode) measured across the thickness of the solid electrolyte layer. In some such embodiments, the first ratio of fluorine atoms to oxygen atoms at a point on one side of the solid electrolyte interface layer (e.g., adjacent to the electrolyte, such as point A in FIG. 3A) within a cross section of the thickness of the solid electrolyte interface layer is substantially higher than the second ratio of fluorine atoms to oxygen atoms on another side of the solid electrolyte interface layer (e.g., adjacent to the anode, such as point B in FIG. 3A). For example, the first ratio (e.g., point A in FIG. 3A) may be at least 25%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 100%, at least 200%, or at least 300% higher than the second ratio (e.g., point B in FIG. 3A). In some embodiments, the first ratio (e.g., point A in FIG. 3A) is no more than 400%, no more than 300%, no more than 200%, no more than 100%, no more than 90%, no more than 80%, no more than 70%, no more than 60%, or no more than 50% higher than the second ratio (e.g., point B in FIG. 3A). Combinations of the above ranges are also possible (e.g., at least 25%, no more than 400%). Other ranges are also possible.

[0022] In some embodiments, a first ratio of fluorine atoms to oxygen atoms at one side of the solid electrolyte interface layer (e.g., at a point adjacent to the electrolyte, such as point A in FIG. 3A ), measured across the thickness of the solid electrolyte interface layer, is higher than the average ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. For example, the first ratio (e.g., point A in FIG. 3A ) may be at least 25%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 100%, at least 200%, or at least 300% higher than the average ratio. In some embodiments, the first ratio (e.g., point A in FIG. 3A ) is no more than 400%, no more than 300%, no more than 200%, no more than 100%, no more than 90%, no more than 80%, no more than 70%, or no more than 60% higher than the average ratio. Combinations of the above ranges are also possible (e.g., at least 25%, no more than 400%). Other ranges are also possible.

[0023] Additionally or alternatively, in some embodiments, the second ratio of fluorine atoms to oxygen atoms at a point adjacent to the anode in a cross section of the thickness of the solid electrolyte interface layer (e.g., point B in FIG. 3A) is substantially smaller than the average ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. For example, the second ratio of fluorine atoms to oxygen atoms at a point adjacent to the anode is at least 25%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% smaller than the average ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. In some embodiments, the second ratio of fluorine atoms to oxygen atoms at a point adjacent to the anode in a cross section of the thickness of the solid electrolyte interface layer (e.g., point B in FIG. 3A) is 100% or less, 90% or less, 80% or less, 70% or less, or 60% or less smaller than the average ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. Combinations of the above ranges are also possible (e.g., 25% or more and 100% or less). Other ranges are also possible.

[0024] The amount of fluorine and oxygen atoms in the solid electrolyte interface layer and in any cross-section of the solid electrolyte interface layer may be measured using a combination of scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX or EDS) techniques. For example, the following procedure may be performed: To measure the amount of fluorine and oxygen atoms, the anode / SEI layer / separator stack, or the anode / SEI and SEI / separator, may be retrieved from cells at various stages of cycle life. The retrieved anode / SEI layer / separator stack may be ion-milled to produce a smooth cross-section and then analyzed by SEM / EDS.

[0025] In some embodiments, the first ratio of fluorine atoms to oxygen atoms is associated with a location relatively close to the surface of the electrolyte (e.g., point A in FIG. 3A). For example, in some embodiments, the first ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer is present at a location that is 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, or 1% or less of the thickness of the solid electrolyte interface layer (e.g., thickness 119 of SEI layer 118 in FIG. 3A) away from the surface of the electrolyte (e.g., surface 123 in FIG. 3A). In some embodiments, the first ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer is associated with a location that is 0% or more, 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more of the thickness of the solid electrolyte interface layer away from the surface of the electrolyte. Combinations of the above ranges are also possible (e.g., 0% or more, 50% or less). Other ranges are also possible. In one set of embodiments, the first ratio of fluorine atoms to oxygen atoms is located directly adjacent to (e.g., in contact with) the surface of the electrolyte.

[0026] In some embodiments, the second ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer is associated with a location (e.g., point B in FIG. 3A) relatively farther from the surface of the electrolyte (or relatively closer to the surface of the anode). For example, in some embodiments, the second ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer is present at a location that is 100% or less, 90% or less, 80% or less, 70% or less, or 60% or less of the thickness of the solid electrolyte interface layer (e.g., thickness 119 of SEI layer 118 in FIG. 3A) away from the surface of the electrolyte (e.g., surface 123 in FIG. 3A). In some embodiments, the second ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer is associated with a location that is 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more of the thickness of the solid electrolyte interface layer away from the surface of the electrolyte. Combinations of the above ranges are also possible (e.g., 50% or more to 100% or less). Other ranges are also possible.

[0027] As an exemplary calculation, if an SEI layer has a thickness of 500 nm and a first ratio of fluorine atoms to oxygen atoms is associated with a location in the SEI layer that is 10% or less of the thickness away from the surface of the electrolyte (e.g., point A in FIG. 3A) and a second ratio of fluorine atoms to oxygen atoms is associated with a location in the SEI layer that is 60% or more of the thickness away from the surface of the electrolyte (e.g., point B in FIG. 3B), then the first ratio of fluorine atoms to oxygen atoms is associated with a location that is 50 nm or less away from the surface of the electrolyte and the second ratio of fluorine atoms to oxygen atoms is associated with a location that is 300 nm or more away from the surface of the electrolyte. Furthermore, if the SEI layer has an average ratio of fluorine atoms to oxygen atoms of 1, and the first ratio of fluorine atoms to oxygen atoms is at least 50% by weight higher than the average ratio and the second ratio of fluorine atoms to oxygen atoms is at least 50% by weight lower than the average ratio, then the first ratio of fluorine atoms to oxygen atoms is at least 1.5 and the second ratio of fluorine atoms to oxygen atoms is less than or equal to 0.5.

[0028] In some embodiments in which the fluorine and oxygen atoms are not substantially uniformly distributed across the thickness of the solid electrolyte interface layer, the ratio of fluorine atoms to oxygen atoms at any given point in a cross-section of the thickness of the solid electrolyte interface layer varies by 50% or more (e.g., 60% or more, 70% or more, 80% or more, or 90% or more) from the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer at any given point in a cross-section of the thickness of the solid electrolyte interface layer. For example, referring again to FIG. 3A , the ratio of fluorine atoms to oxygen atoms at any point A (e.g., adjacent the electrolyte) or the ratio of fluorine atoms to oxygen atoms at any point B (e.g., adjacent the anode) of the cross-section 121 of the solid electrolyte interface layer 118 varies by 50% or more compared to the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer 118. As an exemplary calculation, if a solid electrolyte interface layer has a maximum ratio of fluorine atoms to oxygen atoms of 1, and any point (e.g., point A or point B in FIG. 3A ) within a cross-section (e.g., cross-section 121) through the thickness of the solid electrolyte interface layer has a ratio of 0.5 or less, the solid electrolyte interface layer is considered to be substantially non-uniform, and if any point (e.g., point A or point B in FIG. 3A ) within a cross-section (e.g., cross-section 121) through the thickness of the solid electrolyte interface layer has a ratio of 0.5 or less, the solid electrolyte interface layer is considered to have a substantially non-uniform distribution of fluorine atoms and oxygen atoms through the thickness of the solid electrolyte interface layer based on the maximum ratio of fluorine atoms and oxygen atoms in the solid electrolyte interface layer.

[0029] In some embodiments, a first ratio of fluorine atoms to oxygen atoms at a particular point in a cross-section of the thickness of the solid electrolyte interface layer that is relatively close to the surface of the electrolyte varies substantially less than a maximum ratio of fluorine atoms to oxygen atoms compared to a second ratio of fluorine atoms to oxygen atoms at a point relatively far from the surface of the electrolyte. For example, referring again to FIG. 3A , a first ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point A) in a cross-section of the thickness 119 of the solid electrolyte interface layer 118 that is relatively close to the surface of the electrolyte 14 varies substantially less than a maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer 118 compared to a second ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point B) relatively far from the surface of the electrolyte. For example, in some embodiments, a first ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point A) relatively close to the surface of the electrolyte is at least 10%, at least 20%, at least 30%, at least 50%, at least 70%, or at least 90% less variable than the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer compared to a second ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point B) relatively farther from the surface of the electrolyte. In some embodiments, a first ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point A) relatively close to the surface of the electrolyte is at most 99%, at most 90%, at most 70%, at most 50%, at most 30%, or at most 20% less variable than the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer compared to a second ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point B) relatively farther from the surface of the electrolyte. Combinations of the above ranges are possible (e.g., at least 10%, at most 99%). Other ranges are possible.

[0030] In some embodiments, a first ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point A in FIG. 3A) relatively close to the surface of the electrolyte and within a cross section of the thickness of the solid electrolyte interface layer may have a value that is 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, or 99% or more of a maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. In some embodiments, a particular point (e.g., point A in FIG. 3A) relatively close to the surface of the electrolyte and within a cross section of the thickness of the solid electrolyte interface layer may have a value that is 100% or less, 99% or less, 95% or less, 90% or less, 80% or less, 70% or less, or 60% or less of a maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. Combinations of the above values ​​are also possible (e.g., 50% or more, 100% or less). Other values ​​are also possible. In one set of embodiments, a first ratio of fluorine atoms to oxygen atoms located adjacent (e.g., directly adjacent) to the electrolyte (e.g., point A in FIG. 3A ) is the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer.

[0031] In some embodiments, the second ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point B in FIG. 3A ) relatively far from the surface of the electrolyte (or relatively close to the surface of the anode) within a cross section of the thickness of the solid electrolyte interface layer may have a value of 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, or 45% or more of a maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. In some embodiments, the second ratio of fluorine atoms to oxygen atoms at a particular point (e.g., point B in FIG. 3A ) relatively far from the surface of the electrolyte (or relatively close to the surface of the anode) within a cross section of the thickness of the solid electrolyte interface layer may have a value of 50% or less, 45% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of a maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer. Combinations of the above values ​​are also possible (e.g., 1% or more and 50% or less). Other values ​​are also possible.

[0032] The amounts and ratios (e.g., maximum ratio, average ratio, ratio at any point) of fluorine atoms to oxygen atoms and / or LiF to Li2CO3 (and other oxygen-containing inorganic materials, e.g., Li2O) within a cross-section of the solid electrolyte interface layer may be measured using a combination of scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX or EDS) techniques. The distance between the location containing a particular ratio (e.g., first ratio, second ratio, etc.) of fluorine atoms to oxygen atoms and / or LiF to Li2CO3 (and other oxygen-containing inorganic materials, e.g., Li2O) and the surface of the electrolyte and / or the surface of the anode can be determined in some instances by performing SEM / EDS on ion-milled SEI cross-sections recovered from the electrochemical cell.

[0033] Although FIG. 3A shows an embodiment in which the fluorine and oxygen atoms are not substantially uniformly distributed across the thickness of the solid electrolyte interface layer, embodiments are possible in which the fluorine and oxygen atoms are substantially uniformly distributed across the thickness of the solid electrolyte interface layer. FIG. 3B is a cross-sectional schematic diagram of an embodiment in which the fluorine and oxygen atoms are substantially uniformly distributed across the thickness of the solid electrolyte interface layer. In FIG. 3B, the solid electrolyte interface layer 128 includes Li2CO3 and LiF species that are substantially uniformly distributed within the solid electrolyte interface layer 128 across the thickness 129 of the solid electrolyte interface layer 128. Thus, the ratio of fluorine atoms to oxygen atoms adjacent the electrolyte 14 does not substantially change from the second ratio of fluorine atoms to oxygen atoms adjacent the anode 12 in the solid electrolyte interface layer 128 across the thickness 129 of the solid electrolyte interface layer 128. It should be understood that in addition to LiF and Li2CO3, additional inorganic materials (e.g., Li2O, etc.) may also be present and contribute to the overall ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer.

[0034] In some embodiments in which the fluorine and oxygen atoms are substantially uniformly distributed across the thickness of the solid electrolyte interface layer, the ratio of fluorine atoms to oxygen atoms at any given point in a cross-section of the thickness of the solid electrolyte interface layer varies by no more than 25% (e.g., no more than 20%, no more than 15%, no more than 10%, no more than 5%, no more than 2%, etc.) at any point in the cross-section of the thickness of the solid electrolyte interface layer from the average ratio of fluorine atoms to oxygen atoms measured across the thickness of the solid electrolyte interface layer. For example, referring again to FIG. 3B , the ratio of fluorine atoms to oxygen atoms at any point C or any point D of cross-section 122 of solid electrolyte interface layer 128 may vary by no more than 25% (e.g., no more than 20%, no more than 15%, no more than 10%, no more than 5%, no more than 2%, etc.) at any point in the cross-section of the thickness of the solid electrolyte interface layer. The ratio of fluorine atoms to oxygen atoms varies by no more than 25% compared to the average ratio of fluorine atoms to oxygen atoms in the solid electrolyte layer 128. As an exemplary calculation, if a solid electrolyte interface layer has an average ratio of fluorine atoms to oxygen atoms of 1, and any point in a cross section across the thickness of the solid electrolyte interface layer (e.g., points C or D in FIG. 3B ) has a ratio of 0.75 or greater or 1.25 or less, the solid electrolyte interface layer is considered to have a substantially homogenous distribution of fluorine and oxygen atoms across the thickness of the solid electrolyte interface layer, based on the average ratio of fluorine and oxygen atoms in the solid electrolyte interface layer.

[0035] In some embodiments in which the fluorine and oxygen atoms are substantially uniformly distributed across the thickness of the solid electrolyte interface layer, the ratio of fluorine atoms to oxygen atoms at any given point within a cross-section of the thickness of the solid electrolyte interface layer varies by no more than 50% (e.g., no more than 40%, no more than 30%, no more than 20%, no more than 10%, no more than 5%, etc.) from the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer at any point within a cross-section of the thickness of the solid electrolyte interface layer. For example, referring again to FIG. 3B , the ratio of fluorine atoms to oxygen atoms at any point C, or the ratio of fluorine atoms to oxygen atoms at any point D of the cross-section 122 of the solid electrolyte interface layer 128 varies by no more than 50% compared to the maximum ratio of fluorine atoms to oxygen atoms in the solid electrolyte interface layer 128. As an exemplary calculation, a solid electrolyte interface layer is considered to be substantially homogeneous if it has a maximum ratio of fluorine atoms to oxygen atoms of 1, and all points (e.g., point D in FIG. 3B ) within at least some cross sections (e.g., cross sections 122) across the thickness of the solid electrolyte interface layer have a ratio of 0.5 or greater. If all points (e.g., point D in FIG. 3B ) within at least some cross sections (e.g., cross sections 122) across the thickness of the solid electrolyte interface layer have a ratio of 0.5 or greater, the solid electrolyte interface layer is considered to have a substantially homogeneous distribution of fluorine atoms and oxygen atoms across the thickness of the solid electrolyte interface layer based on the maximum ratio of fluorine atoms and oxygen atoms in the solid electrolyte interface layer.

[0036] In some embodiments, disclosed herein is a method for storing and using electrical energy in an electrochemical cell. In some embodiments, the method includes applying an anisotropic force to the cell, applying a formation voltage to the cell, and forming an SEI layer as described herein in the cell, as described in more detail below.

[0037] In some embodiments, a method of storing and using electrical energy in an electrochemical cell includes applying an anisotropic force to a surface (e.g., active surface) of an anode. In some such embodiments, the electrochemical cell includes an anode including lithium metal, lithium alloy, or a combination thereof as an anode active material, a cathode, and an electrolyte including a fluorinated organic solvent disposed between the anode and the cathode. In some embodiments, the anode has a surface adjacent to the electrolyte, such as, for example, the active surface of the electrode where an electrochemical reaction may occur. For example, as shown in FIG. 1, an electrochemical cell 10 includes an anode 12 having a surface 24, a cathode 16, and an electrolyte 14 including a fluorinated organic solvent disposed between the anode 12 and the cathode 16. In some such embodiments, application of an anisotropic force to a surface (e.g., active surface) of the anode can enhance the performance (e.g., discharge resistance, cycle life, etc.) of the electrochemical cell, as described elsewhere herein.

[0038] In some embodiments, applying an anisotropic force to a surface (e.g., active surface) of the anode includes applying an anisotropic force during at least one period during a charge cycle and a discharge cycle. In some embodiments, the force may be applied continuously, over a period, or over multiple periods of varying duration and / or period. The anisotropic force may optionally be applied at one or more predefined locations, and may optionally be distributed over the surface of the anode. In some embodiments, the anisotropic force is applied uniformly over the surface (e.g., active surface) of the anode.

[0039] For example, the at least one period may include an initial formation cycle (e.g., a charge-discharge cycle during which a stable solid electrolyte interfacial layer forms in the cell) and / or a subsequent charge-discharge cycle. In one set of embodiments, the application of an anisotropic force to the surface of the anode persists throughout the entire period of cycling (e.g., all formation cycles and subsequent charge-discharge cycles).

[0040] In some embodiments, the force comprises an anisotropic force having a component perpendicular to a surface (e.g., active surface) of the anode. In the case of a flat surface, the force may comprise an anisotropic force having a component perpendicular to the surface at the point at which the force is applied. For example, with reference to FIG. 1, the force may be applied in the direction of arrow 26. Arrow 28 indicates the component of the force perpendicular to surface 24 of anode 12. As shown, surface 24 of anode 12 is the surface opposite anode current collector 22 and configured to face cathode 16. In the case of a curved surface, e.g., concave or convex, the force may comprise an anisotropic force having a component perpendicular to a plane tangent to the curved surface at the point at which the force is applied.

[0041] In some cases, one or more forces applied to the cell have a component that is not perpendicular to the surface (e.g., active surface) of the anode. For example, in FIG. 1, instead of force 26 being perpendicular to anode surface 24, force 26 includes a component 30 that is substantially parallel to anode surface 24. Additionally, in some cases, a force 25 that is substantially parallel to anode surface 24 may be applied to the cell. In one set of embodiments, the sum of all anisotropic force components applied in a direction perpendicular to the anode surface is greater than the sum of any components in a direction that is not perpendicular to the anode surface. In some embodiments, the sum of all applied anisotropic force components in a direction perpendicular to the anode surface is at least about 5%, at least about 10%, at least about 20%, at least about 35%, at least about 50%, at least about 75%, at least about 90%, at least about 95%, at least about 99%, or at least about 99.9% greater than any sum of components in a direction parallel to the anode surface.

[0042] In some embodiments, the application of an anisotropic force during at least one period during charging and / or discharging of the cell is associated with the formation of a solid electrolyte interface layer (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) having a particular set of advantageous properties at the anode and electrolyte interface. For example, in one set of embodiments, the application of anisotropic pressure may result in the formation of a stable and controlled solid electrolyte interface layer (e.g., SEI layer 18 of FIG. 1) having a relatively high conformality to the anode surface, such that the solid electrolyte interface layer can effectively protect the anode from adverse reactions and / or degradation. Furthermore, the application of an anisotropic force during cycling can help regulate the growth of resistive SEI buildup during cycling, thereby reducing the rate of increase of discharge resistance and inhibiting polarization of the cell during cycling. As a result, the cell can exhibit enhanced cycle life.

[0043] In some embodiments, an anisotropic force having a component perpendicular to a surface (e.g., active surface) of the anode is applied to an extent effective to inhibit an increase in the surface area of ​​the anode surface (e.g., active surface) relative to the increase in surface area in the absence of the anisotropic force, during at least one period during charging and / or discharging of the electrochemical device.

[0044] In some embodiments, the component of the anisotropic force perpendicular to the surface (e.g., active surface) of the electrode is at least about 1 kg / cm 2 , at least about 2 kg / cm 2 , at least about 4 kg / cm 2 , at least about 6 kg / cm 2 , at least about 6 kg / cm 2 , at least about 7 kg / cm 2 , at least about 8 kg / cm 2 , at least about 10 kg / cm 2 , at least about 12 kg / cm 2 , at least about 14 kg / cm 2 , at least about 16 kg / cm 2 , at least about 18 kg / cm 2 , at least about 20 kg / cm2 , at least about 22 kg / cm 2 , at least about 24 kg / cm 2 , at least about 26 kg / cm 2 , at least about 28 kg / cm 2 , at least about 30 kg / cm 2 , at least about 32 kg / cm 2 , at least about 34 kg / cm 2 , at least about 36 kg / cm 2 , at least about 38 kg / cm 2 , at least about 40 kg / cm 2 , at least about 42 kg / cm 2 , at least about 44 kg / cm 2 , at least about 46 kg / cm 2 , or at least about 48 kg / cm 2 In some embodiments, the component of the anisotropic force normal to the surface is, for example, about 50 kg / cm 2 Less than 48kg / cm 2 Less than 46kg / cm 2 Less than 44kg / cm 2 Less than 42kg / cm 2 Less than 40kg / cm 2 Less than 38kg / cm 2 Less than 36kg / cm 2 Less than 34kg / cm 2 Less than 32kg / cm 2 Less than 30kg / cm 2 Less than 28kg / cm 2 Less than 26kg / cm 2 Less than 24kg / cm 2 Less than 22kg / cm 2 Less than 20kg / cm 2 Less than 18kg / cm 2 Less than 16kg / cm 2 Less than 14kg / cm 2 Less than 12kg / cm 2 Less than 10kg / cm 2 Less than 8kg / cm 2 Less than 7kg / cm 2 Less than 6kg / cm2 Less than 4kg / cm 2 Less than or about 2kg / cm 2 Combinations of the above ranges are also possible (e.g., at least about 7 kg / cm 2 About 50kg / cm or more 2 Less than 8kg / cm 2 Approximately 30kg / cm 2 Less than about 10 kg / cm 2 Approximately 25kg / cm 2 Other ranges are possible.

[0045] Although force and pressure are commonly described in units of Newtons and Newtons per unit area, respectively, force and pressure can also be expressed in units of kilogram-force and kilogram-force per unit area (i.e., kgf / cm). 2 or kg / cm 2 Those skilled in the art are familiar with kilogram-force based units and understand that 1 kilogram-force is equivalent to approximately 9.8 Newtons.

[0046] In some embodiments, a method for storing and using electrical energy in an electrochemical cell includes applying a formation voltage during at least one period during charging and / or discharging the cell. In some such embodiments, the at least one period during charging and / or discharging is associated with a formation cycle, i.e., an initial charge and / or discharge cycle associated with the formation of a stable solid electrolyte interfacial layer. For example, in some embodiments, the formation cycle occurs for at least the (first) 1 cycle, at least the (first) 2 cycles, at least the (first) 3 cycles, at least the (first) 4 cycles, or at least the (first) 5 cycles of charging and discharging the cell. In some embodiments, the formation cycle occurs for no more than the (first) 6 cycles, no more than the (first) 5 cycles, no more than the (first) 4 cycles, no more than the (first) 3 cycles, or no more than the (first) 2 cycles of charging and discharging the cell. Combinations of the above ranges are also possible (e.g., 1 to 5 cycles, 1 to 4 cycles, 1 to 3 cycles). Other ranges are also possible.

[0047] According to some embodiments, the formation voltage is the voltage applied during the formation cycle. For example, in one set of embodiments, the formation voltage is applied for 1 or more, 2 or more, 3 or more, 4 or more, or 5 or more cycles of charging and discharging the cell. In some embodiments, the formation voltage is applied for 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less cycles of charging and discharging the cell. Combinations of the above ranges are also possible (e.g., 1 or more and 5 or less, 1 or more and 4 or less, 1 or more and 3 or less). Other ranges are also possible.

[0048] In some embodiments, the formation of Li2CO3 in the solid electrolyte interface layer (e.g., as shown in FIG. 3A) is associated with a relatively high formation voltage applied during at least one period during charging and / or discharging of the cell. In some such embodiments, the relatively high formation voltage may favorably initiate the reaction forming Li2CO3 in the SEI layer and / or increase the rate of formation of Li2CO3, resulting in the presence of a significant amount of Li2CO3 in the solid electrolyte interface layer. The presence of a relatively high loading of Li2CO3 in the solid electrolyte interface layer may result in improved performance (e.g., anode stability, cycle life, etc.) of the electrochemical cell.

[0049] In some embodiments, the relatively high formation voltage is 4.35V or more, 4.4V or more, 4.45V or more, 4.5V or more, 4.55V or more, 4.6V or more, 4.65V or more, 4.7V or more, 4.75V or more, 4.8V or more, 4.85V or more, 4.9V or more, or 4.95V. In some embodiments, the relatively high formation voltage is 5V or less, 4.95V or less, 4.9V or less, 4.85V or less, 4.8V or less, 4.75V or less, 4.7V or less, 4.65V or less, 4.6V or less, 4.55V or less, 4.5V or less, or 4.45V or less. Combinations of the above ranges are also possible (e.g., 4.4V or more and 5V or less, 4.5V or more and 4.9V or less, or 4.55V or more and 4.75V or less). Other ranges are also possible.

[0050] In some embodiments, the relatively high formation voltage may be applied for any of a variety of durations. For example, in one set of embodiments, the formation voltage may be applied for a total of 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 60 minutes or more, 120 minutes or more, 180 minutes or more, 360 minutes or more, 540 minutes or more, 720 minutes or more, 900 minutes or more, 1080 minutes or more, or 1260 minutes or more. In some embodiments, the formation voltage may be applied for a total of 1440 minutes or less, 1260 minutes or less, 1080 minutes or less, 900 minutes or less, 720 minutes or less, 540 minutes or less, 360 minutes or less, 180 minutes or less, 120 minutes or less, 60 minutes or less, 30 minutes or less, 20 minutes or less, 15 minutes or less, 10 minutes or less, or 5 minutes or less. Combinations of the above ranges are also possible (eg, 1 to 1440 minutes, 5 to 720 minutes, or 10 to 360 minutes). Other ranges are also possible.

[0051] In some embodiments, application of an anisotropic force and application of a high formation voltage during at least one period during charging and / or discharging of the cell is associated with the formation of a solid electrolyte interfacial layer (e.g., as shown in FIG. 3A) comprising LiF and Li2CO3 having advantageous properties, including, but not limited to, high compatibility with the anode, high stability, high ionic conductivity, etc. Application of an anisotropic force during formation and / or subsequent discharge and / or charge cycles can further improve the performance of the electrochemical cell (e.g., slower rate of resistive SEI buildup and discharge resistance growth, improved cycle life, etc.).

[0052] In some embodiments, a method of storing and using electrical energy in an electrochemical cell includes forming a solid electrolyte interface layer adjacent a surface (e.g., an active surface) of an anode. In some such embodiments, a solid electrolyte interface layer comprising one or more inorganic materials (e.g., LiF, Li2CO3, Li2O, etc.) is formed in situ during charging and / or discharging of the electrochemical cell. For example, referring again to FIG. 1, an electrochemical cell 100, upon being charged and / or discharged, results in the in situ formation of a solid electrolyte interface layer 18 adjacent a surface 24 of an anode 12. In some such embodiments, the controlled formation of the solid electrolyte interface layer is associated, at least in part, with the application of an anisotropic force and / or formation voltage during the charge and / or discharge cycles.

[0053] In some embodiments, the solid electrolyte interfacial layer comprises inorganic materials including LiF and / or Li2CO3 (e.g., as shown in Figures 2-3). Depending on the type of inorganic material, the pathway by which these inorganic materials are formed may vary. For example, in one set of embodiments, LiF is formed in situ as a result of decomposition of one or more fluorinated electrolyte solvents during charging and / or discharging (e.g., as shown in Figures 2-3).

[0054] In one set of embodiments, Li2CO3 is formed in situ by reaction of CO2 with lithium metal on the anode surface (e.g., as shown in FIG. 3). For example, CO2 may be generated during charging and / or discharging from various components of the cell, such as decomposition of the electrolyte solvent (e.g., ester-based, carbonate-based solvents) and / or gassing from the cathode (e.g., impurities in the NCM cathode) during cycling. As described above and with respect to FIG. 3, the in-situ formation of a solid electrolyte interface layer containing a relatively high loading of Li2CO3 may be caused, at least in part, by a high formation voltage applied during at least one period (e.g., formation cycle) during charging and / or discharging of the cell. The solid electrolyte interface layer may further include one or more inorganic materials (e.g., lithium alkoxides, lithium oxides, lithium salts, and other decomposition products of the electrolyte) as a result of charging and / or discharging of the cell.

[0055] Although the present disclosure generally describes in-situ formation of a solid electrolyte interface layer during charging and / or discharging, in some cases, at least a portion of the solid electrolyte interface layer may be formed ex situ. In some such embodiments, a portion of the solid electrolyte interface layer comprising Li2CO3 is formed by pre-passivation of the anode (e.g., the electroactive layer of the anode) with CO2 prior to assembly of the electrochemical cell. In some such embodiments, after assembly of the pre-passivated anode into the electrochemical cell, an additional solid electrolyte interface layer comprising LiF and / or Li2CO3 may be formed in situ in the manner described above.

[0056] In some embodiments, the solid electrolyte interface layer comprises a relatively high loading of inorganic material. In some such embodiments, the solid electrolyte interface layer comprises a total amount of inorganic material of 10 wt% or more, 20 wt% or more, 30 wt% or more, 40 wt% or more, 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more. In some embodiments, the solid electrolyte interface layer comprises a total amount of inorganic material of 100 wt% or less, 90 wt% or less, 80 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, or 20 wt% or less. Combinations of the above ranges are also possible (e.g., 10 wt% or more and 100 wt% or less). Other ranges are also possible.

[0057] In some embodiments, the solid electrolyte interface layer includes a relatively high amount of fluorine-containing inorganic material (e.g., LiF). In some such embodiments, the solid electrolyte interface layer includes fluorine-containing inorganic material (e.g., LiF) in an amount of 10 wt% or more, 20 wt% or more, 30 wt% or more, 40 wt% or more, 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more. In some embodiments, the solid electrolyte interface layer may include fluorine-containing inorganic material (e.g., LiF) in an amount of 100 wt% or less, 90 wt% or less, 80 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, or 20 wt% or less. Combinations of the above ranges are also possible (e.g., 10 wt% or more to 100 wt% or less). Other ranges are also possible. In some embodiments, the SEI layer may include additional fluorine-containing inorganic materials in association with the presence of fluorine-containing salts and / or fluorine-containing additives (e.g., LixPFy, LixPOyFz, etc.).

[0058] In some embodiments, the solid electrolyte interface layer comprises a relatively high amount of Li2CO3. In some such embodiments, the solid electrolyte interface layer comprises Li2CO3Li2CO3 in an amount of 10 wt% or more, 20 wt% or more, 30 wt% or more, 40 wt% or more, 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more. In some embodiments, the solid electrolyte interface layer comprises Li2CO3 in an amount of 100 wt% or less, 90 wt% or less, 80 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, or 20 wt% or less. Combinations of the above ranges are also possible (e.g., 10 wt% or more and 100 wt% or less). Other ranges are also possible.

[0059] In some embodiments, the solid electrolyte interface layer includes relatively high amounts of both LiF and Li2CO3. In some such embodiments, LiF and Li2CO3 may be present independently, in any amount previously described, or in combination.

[0060] The solid electrolyte interface layer may include LiF and Li2CO3 in any of a variety of suitable weight ratios. In some embodiments, the weight ratio of LiF to Li2CO3 may be 1:100 or more, 1:50 or more, 1:10 or more, 1:5 or more, 1:2 or more, 1:1 or more, 2:1 or more, 3:1 or more, 5:1 or more, 10:1 or more, 25:1 or more, 50:1 or more, or 75:1 or more. In some embodiments, the weight ratio of LiF to Li2CO3 may be 100:1 or less, 75:1 or less, 50:1 or less, 25:1 or less, 10:1 or less, 5:1 or less, 3:1 or less, 2:1 or less, 1:1 or less, 1:2 or less, 1:5 or less, 1:10 or less, or 1:50 or less. Combinations of the above ranges are also possible (e.g., 1:100 or more, 100:1 or less). Other ranges are also possible.

[0061] In some embodiments, other inorganic materials, such as Li2O, may be formed in the SEI layer in any of a variety of suitable amounts. For example, the formation of Li2O may be associated with the presence of a fluorinated solvent (e.g., fluoroethylene carbonate) and / or a passivator (e.g., LiBOB). In some such embodiments, Li2O may be formed in any of a variety of suitable amounts. For example, in some embodiments, the solid electrolyte interface layer includes Li2O in an amount of 5 wt% or more, 10 wt% or more, 20 wt% or more, 30 wt% or more, 40 wt% or more, or 50 wt% or more. In some embodiments, the solid electrolyte interface layer includes Li2O in an amount of 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, 20 wt% or less, or 10 wt% or less. Combinations of the above ranges are also possible (e.g., 10 wt% or more and 50 wt% or less, or 5 wt% or more and 50 wt% or less). Other ranges are also possible.

[0062] In some embodiments, the solid electrolyte interface layer may include LiF and Li2O in any of a variety of suitable weight ratios. In some embodiments, the weight ratio of LiF to Li2O may be 1:5 or more, 1:4 or more, 1:3 or more, 1:2 or more, 1:1 or more, 2:1 or more, 3:1 or more, 5:1 or more, 10.1 or more, 25:1 or more, 50.1 or more, or 75:1 or more. In some embodiments, the weight ratio of LiF to Li2O may be 10.01 or less, 75:1 or less, 50.1 or less, 25:1 or less, 10.1 or less, 5:1 or less, 3:1 or less, 2:1 or less, 1:1 or less, 1:2 or less, 1:3 or less, or 1:4 or less. Combinations of the above ranges are also possible (e.g., 1:5 or more and 100:1 or less, or 1:5 or more and 2:1 or less). Other ranges are also possible.

[0063] In some embodiments, at least a portion of the inorganic material (eg, LiF, Li2O, Li2CO3, etc.) in the solid electrolyte interface layer may be in crystalline form.

[0064] In some embodiments, at least a portion of the inorganic material may be in nanocrystalline form. In some embodiments, the solid electrolyte interface layer may include nanocrystalline inorganic material having a size (e.g., diameter, width, length, etc.) of 5 nm or more, 7.5 nm or more, 10 nm or more, 12.5 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, or 35 nm or more. In some embodiments, the solid electrolyte interface layer may include nanocrystalline inorganic material having a size (e.g., diameter, width, length, etc.) of 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 15 nm or less, 12.5 nm or less, or 10 nm or less, or 7.5 nm or less. Combinations of the above ranges are also possible (e.g., 5 nm or more and 40 nm or less, or 10 nm or more and 25 nm or less). Other ranges are also possible.

[0065] For example, in one set of embodiments, at least 5%, at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 70%, at least 80%, or at least 90% of the LiF in the solid electrolyte interface layer is in crystalline form. For example, in some embodiments, no more than 100%, no more than 90%, no more than 80%, no more than 70%, no more than 60%, no more than 50%, no more than 40%, no more than 30%, no more than 20%, or no more than 10% of the LiF in the solid electrolyte interface layer is in crystalline form. Combinations of the above ranges are also possible (e.g., 5% or more, 100% or less). Other ranges are also possible.

[0066] In one set of embodiments, at least 5%, at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 70%, at least 80%, or at least 90% of the Li2O in the solid electrolyte interface layer is in crystalline form. For example, in some embodiments, 100% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the Li2O in the solid electrolyte interface layer is in crystalline form. Combinations of the above ranges are also possible (e.g., 5% or more, 100% or less). Other ranges are also possible.

[0067] The solid electrolyte interface layer may have any of a variety of suitable porosities. In some embodiments, the SEI layer may have a relatively high porosity such that the SEI layer can facilitate efficient ion transport across the SEI layer. In some such embodiments, the solid electrolyte interface layer comprising LiF has a porosity of 1% or more, 5% or more, 10% or more, 15% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, or 80% or more. In some embodiments, the solid electrolyte interface layer has a porosity of 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. Combinations of the above ranges are also possible (e.g., 10% or more, 90% or less). Other ranges are also possible.

[0068] The solid electrolyte interface layer may have any of a variety of suitable hardness values. In some embodiments, the solid electrolyte interface layer has a hardness of 0.001 GPa or more, 0.005 GPa or more, 0.01 GPa or more, 0.05 GPa or more, 0.1 GPa or more, 0.5 GPa or more, 1 GPa or more, 1.5 GPa or more, 2 GPa or more, 2.5 GPa or more, 3 GPa or more, 3.5 or more, 4 GPa or more, or 5 GPa or more. In some embodiments, the solid electrolyte interface layer has a hardness of 10 GPa or less, 5 GPa or less, 4.5 GPa or less, 4 GPa or less, 3.5 GPa or less, 3 GPa or less, 2.5 GPa or less, 2 GPa or less, 1.5 GPa or less, 1 GPa or less, 0.5 GPa or less, 0.1 GPa or less, 0.05 GPa or less, 0.01 GPa or less, or 0.005 GPa or less. Combinations of the above ranges are also possible (eg, greater than or equal to 0.001 GPa and less than or equal to 5 GPa). Other ranges are also possible.

[0069] Hardness values ​​can be measured with a nano hardness tester using a Berkovitch tip. A load of 0.5N to 2.5N may be used to maintain a penetration depth into the SEI layer. Hardness values ​​may be measured according to the methods disclosed in ASTM E2546 and ISO 14577-4. Methods for measuring hardness include, but are not limited to, Rockwell, Vickers, Martens, etc.

[0070] For example, the solid electrolyte interface layer may have any of a variety of suitable Vickers Pyramid Number (HV) values. For example, the solid electrolyte interface layer can have a Vickers Pyramid Number of 0.1 or more, 1 or more, 5 or more, 10 or more, 20 or more, 30 or more, 50 or more, or 70 or more. In some embodiments, the solid electrolyte interface layer has a Vickers Pyramid Number (HV) of 90 or less, 70 or less, 50 or less, 30 or less, 10 or less, 5 or less, or 1 or less. Combinations of the above ranges are also possible (e.g., 1 or more and 90 or less). Other ranges are also possible.

[0071] For example, the solid electrolyte interface layer may have any of a variety of suitable Martens hardness numbers. For example, the solid electrolyte interface layer may have a Martens hardness number of 0.0003 or more, 0.0005 or more, 0.001 or more, 0.005 or more, 0.01 or more, 0.05 or more, 0.1 or more, or 0.3 or more. In some embodiments, the solid electrolyte interface layer has a Martens hardness number of 0.5 or less, 0.3 or less, 0.1 or less, 0.05 or less, 0.01 or less, 0.005 or less, 0.001 or less, or 0.0005 or less. Combinations of the above ranges are also possible (e.g., 0.0003 or more and 0.5 or less). Other ranges are also possible.

[0072] The solid electrolyte interface layer may have any of a variety of suitable thicknesses. For example, the solid electrolyte interface layer may have a thickness of 10 nm or more, 20 nm or more, 50 nm or more, 100 nm or more, 200 nm or more, 500 nm or more, 1 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 50 μm or more, 75 μm or more, or 100 μm or more (e.g., as shown by thicknesses 19, 119, and 129 in Figures 1-3). In some embodiments, the solid electrolyte interface layer may have a thickness of 200 μm or less, 100 μm or less, 75 μm or less, 50 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, 5 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, 200 nm or less, 100 nm or less, 50 nm or less, or 20 nm or less. Combinations of the above ranges are also possible (e.g., 10 nm or more and 200 μm or less, 10 nm or more and 75 μm or less, or 10 nm or more and 50 μm or less). Other ranges are also possible.

[0073] The solid electrolyte interface layer may have any of a variety of suitable bulk densities. In some embodiments, the solid electrolyte interface layer may have a relatively high bulk density. In some embodiments, the solid electrolyte interface layer may have a bulk density of 0.5 g / cm. 3 More than 1.0g / cm 3 More than 1.5g / cm 3 More than 2.0g / cm 3 More than 2.5g / cm 3 More than 3.0g / cm 3 More than 4.0g / cm 3 More than 5.0g / cm 3 In some embodiments, the solid electrolyte interfacial layer may have a bulk density of 7.5 g / cm or greater. 3 Below, 5.0g / cm 3 Below, 4.0g / cm 3 Below 3.0g / cm 3 Below 2.5g / cm 3 Below 2.0g / cm 3 Below 1.5g / cm 3 or less than 1g / cm 3Combinations of the above ranges are also possible (e.g., 0.5 g / cm 3 More than 7.5g / cm 3 or less than 1g / cm 3 More than 3g / cm 3 (See below). Other ranges are possible.

[0074] The solid electrolyte interface layer may have any of a variety of suitable elastic modulus values. For example, the solid electrolyte interface layer may have an elastic modulus of 0.003 GPa or more, 0.005 GPa or more, 0.01 GPa or more, 0.05 GPa or more, 0.1 GPa or more, 0.5 GPa or more, 1 GPa or more, 1.5 GPa or more, 2 GPa or more, 2.5 GPa or more, 3 GPa or more, 3.5 GPa or more, or 4 GPa or more. In some embodiments, the solid electrolyte interface layer has an elastic modulus of 5 GPa or less, 4.5 GPa or less, 4 GPa or less, 3.5 GPa or less, 3 GPa or less, 2.5 GPa or less, 2 GPa or less, 1.5 GPa or less, 1 GPa or less, 0.5 GPa or less, 0.1 GPa or less, 0.05 GPa or less, 0.01 GPa or less, or 0.005 GPa or less. Combinations of the above ranges are also possible (e.g., 0.003 GPa or more, 5 GPa or less). Other ranges are possible.

[0075] In some embodiments, the solid electrolyte interface layer (e.g., adjacent to the electrolyte and / or electrolyte-impregnated separator) comprises particles (e.g., crystalline particles) having any of a variety of suitable sizes. In some embodiments, the solid electrolyte interface layer adjacent to the electrolyte comprises particles having a size of 10 nm or more, 20 nm or more, 40 nm or more, 60 nm or more, 80 nm or more, 100 nm or more, 125 nm or more, 150 nm or more, 175 nm or more, or 200 nm or more. In some embodiments, the solid electrolyte interface layer adjacent to the electrolyte comprises particles having a size of 250 nm or less, 200 nm or less, 175 nm or less, 150 nm or less, 125 nm or less, 100 nm or less, 80 nm or less, 60 nm or less, 40 nm or less, or 20 nm or less. Combinations of the above ranges are also possible (e.g., 10 nm or more and 200 nm or less). Other ranges are also possible.

[0076] In some embodiments, electrochemical cells including a solid electrolyte interface layer as described herein exhibit a slower rate of discharge capacity decay compared to an otherwise comparable electrochemical cell that does not include such a solid electrolyte interface layer. The discharge capacity, C, is calculated according to the following formula (1): C=I dch t (1) According to the current I dch The discharge capacity can be calculated by multiplying the time t to reach the discharge voltage cutoff after cycling. As cycling continues, the discharge capacity can be determined for each subsequent cycle.

[0077] In some embodiments, the electrochemical cell exhibits a decrease in discharge capacity of 0% or more, 0.01% or more, 0.05% or more, 0.1% or more, 0.5% or more, 1% or more, 1.5% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, or 15% or more after 100 charge / discharge cycles relative to the discharge capacity at the fifth charge / discharge cycle after formation (e.g., formation cycle). In some embodiments, the electrochemical cell exhibits a decrease in discharge capacity of 20% or less, 15% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.1% or less, 0.05% or less, or 0.01% or less relative to the discharge capacity at the fifth charge / discharge. Combinations of the above ranges are also possible (e.g., 0% or more and 20% or less). Other ranges are also possible.

[0078] In some embodiments, electrochemical cells including a solid electrolyte interface layer as described herein exhibit a slower rate of increase in discharge resistance compared to an otherwise comparable electrochemical cell that does not include such a solid electrolyte interface layer. The discharge resistance of an electrochemical cell during cycling may be measured by the following general procedure (or protocol). First, the electrochemical cell can be connected to a battery cycler channel capable of supplying the electrochemical cell with a manufacturer-specified current and voltage. The cell is first discharged at the manufacturer-specified current to a manufacturer-specified voltage and then rested for a period of time (e.g., at least 2 minutes). The cell is then charged at the manufacturer-specified current to a manufacturer-specified voltage, the voltage is held at the specified voltage until the current decays to a particular value, and the cell is again rested for a period of time (e.g., at least 2 minutes). The rest voltage (V1) is measured at the end of this rest period. The cell is then discharged again at the manufacturer-specified current to the specified voltage. The voltage (V2) can be measured 5 minutes after this discharge. The discharge resistance, also known as the 5-minute discharge resistance R, is calculated using the following formula (2): R=(V2-V1) / I dch (2) (Where V1 is the voltage at the end of the pause before discharge, V2 is the voltage measured 5 minutes after the start of discharge, and I dch is the discharge current (A). As the cycles continue, the discharge resistance can be determined for each subsequent cycle.

[0079] In some such embodiments, the electrochemical cell exhibits an increase in discharge resistance of 0% or more, 0.01% or more, 0.05% or more, 0.1% or more, 0.5% or more, 1% or more, 1.5% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, or 15% or more after 100 charge / discharge cycles relative to the discharge resistance at the fifth charge / discharge cycle after formation. In some embodiments, the electrochemical cell exhibits an increase in discharge resistance of 20% or less, 15% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.1% or less, 0.05% or less, or 0.01% or less after 100 charge / discharge cycles relative to the discharge resistance at the fifth charge / discharge cycle after formation. Combinations of the above ranges are also possible (e.g., 0% or more and 20% or less). Other ranges are possible.

[0080] In some embodiments, electrochemical cells comprising the solid electrolyte interface layer described herein (e.g., comprising one or more of LiF, Li2CO3, Li2O, etc.) exhibit improved cycle life. In some embodiments, electrochemical cells comprising the solid electrolyte interface layer described herein exhibit cycle life of 100 cycles or more, 150 cycles or more, 200 cycles or more, 250 cycles or more, 300 cycles or more, 350 cycles or more, 400 cycles or more, 450 cycles or more, 500 cycles or more, 1000 cycles or more, or 1500 cycles or more. In some embodiments, electrochemical cells comprising the solid electrolyte interface layer described herein exhibit cycle life of 2000 cycles or less, 1500 cycles or less, 1000 cycles or less, 500 cycles or less, 450 cycles or less, 400 cycles or less, 350 cycles or less, 300 cycles or less, 250 cycles or less, 200 cycles or less, or 150 cycles or less. Combinations of the above ranges are also possible (e.g., 100 cycles or more, 2000 cycles or less). Other ranges are possible.

[0081] In some embodiments, electrochemical cells including a solid electrolyte interface layer described herein (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) exhibit improved cycle life as compared to an otherwise comparable electrochemical cell that does not include such a solid electrolyte interface layer. In some embodiments, electrochemical cells including a solid electrolyte interface layer described herein exhibit cycle life that is at least 2 times, at least 3 times, at least 5 times, at least 10 times, at least 15 times, at least 20 times, at least 25 times, at least 30 times, at least 40 times, at least 50 times, at least 100 times, at least 200 times, at least 300 times, or at least 400 times the cycle life of an otherwise comparable electrochemical cell that does not include a solid electrolyte interface layer. In some embodiments, electrochemical cells comprising a solid electrolyte interface layer as described herein exhibit cycle lives that are 500 times or less, 400 times or less, 300 times or less, 200 times or less, 100 times or less, 50 times or less, 40 times or less, 30 times or less, 20 times or less, 10 times or less, or 3 times or less than the cycle life of an otherwise comparable electrochemical cell that does not comprise a solid electrolyte interface layer. Combinations of the above ranges are also possible (e.g., 2 times or more, 500 times or less). Other ranges are also possible.

[0082] In some embodiments, electrochemical cells including solid electrolyte interface layers (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) with application of an anisotropic force during at least a period of charge-discharge cycling exhibit improved physical properties compared to cells including solid electrolyte interface layers without application of an anisotropic force. In some embodiments, electrochemical cells including solid electrolyte interface layers described herein (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) with application of an anisotropic force during at least a period of charge-discharge cycling exhibit cycle life that is at least 2 times, at least 3 times, at least 5 times, at least 10 times, at least 15 times, at least 20 times, at least 25 times, at least 30 times, at least 40 times, at least 50 times, at least 100 times, at least 200 times, at least 300 times, or at least 400 times. In some embodiments, electrochemical cells including a solid electrolyte interface layer as described herein with application of an anisotropic force at least during charge-discharge cycling exhibit cycle lives that are 500 times or less, 400 times or less, 300 times or less, 200 times or less, 100 times or less, 50 times or less, 40 times or less, 30 times or less, 20 times or less, 10 times or less, or 3 times or less than the cycle life of an otherwise comparable electrochemical cell with a solid electrolyte interface layer but formed without the application of pressure. Combinations of the above ranges are also possible (e.g., 2 times or more, 500 times or less). Other ranges are also possible. The magnitude of the applied anisotropic force may be one or more of the ranges described herein.

[0083] In some embodiments, electrochemical cells including a solid electrolyte interface layer formed in the presence of a fluorinated electrolyte solvent (e.g., comprising one or more of LiF, Li2CO3, Li2O, etc.) and subjected to an applied anisotropic force for at least the duration of a charge-discharge cycle exhibit improved physical properties compared to an otherwise comparable cell including a solid electrolyte interface layer formed in the presence of a non-fluorinated electrolyte solvent and subjected to the same applied anisotropic force. For example, compared to a solid electrolyte interface layer of a cell including a non-fluorinated electrolyte and subjected to the anisotropic force, a solid electrolyte interface layer of an electrochemical cell including a fluorinated electrolyte solvent and subjected to the same anisotropic force may exhibit a more gradual increase in thickness and / or a more gradual decrease in bulk density over charge-discharge cycles. These differences in physical properties may contribute, at least in part, to improved cycle life.

[0084] In some embodiments, electrochemical cells including a solid electrolyte interface layer (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) formed under high formation voltages exhibit improved physical properties as compared to an otherwise comparable electrochemical cell including a solid electrolyte interface layer but formed without the high formation voltage. In some embodiments, electrochemical cells including a solid electrolyte interface layer described herein (e.g., including one or more of LiF, Li2CO3, Li2O, etc.) formed under high formation voltages exhibit cycle lives that are at least 2 times, at least 3 times, at least 5 times, at least 10 times, at least 15 times, at least 20 times, at least 25 times, at least 30 times, at least 40 times, at least 50 times, at least 100 times, at least 200 times, at least 300 times, or at least 400 times greater than the cycle life of an otherwise comparable electrochemical cell including a solid electrolyte interface layer but formed without the high formation voltage. In some embodiments, electrochemical cells including a solid electrolyte interface layer formed under high formation voltages exhibit cycle lives that are 500 times or less, 400 times or less, 300 times or less, 200 times or less, 100 times or less, 50 times or less, 40 times or less, 30 times or less, 20 times or less, 10 times or less, or 3 times or less than the cycle life of an otherwise comparable electrochemical cell including a solid electrolyte interface layer but formed without the high formation voltage. Combinations of the above ranges are also possible (e.g., 2 times or more, 500 times or less). Other ranges are also possible.

[0085] In some embodiments, electrochemical cells including a solid electrolyte interface layer (e.g., rich in one or more of LiF, Li2CO3, Li2O, etc.) help preserve charge / discharge capacity in the electrochemical cell at relatively low temperatures (e.g., 0° C. or less, −25° C. or less, −40° C. or less, etc.). In some such embodiments, when charged and discharged at relatively low temperatures, electrochemical cells including a solid electrolyte interface layer described herein exhibit improved cycle life of 60 cycles or more, 80 cycles or more, 90 cycles or more, 100 cycles or more, 125 cycles or more, 150 cycles or more, 250 cycles or more, 500 cycles or more, or 750 cycles or more. In some embodiments, when charged and discharged at relatively low temperatures, electrochemical cells including a solid electrolyte interface layer described herein exhibit cycle life of 1000 cycles or less, 750 cycles or less, 500 cycles or less, 250 cycles or less, 175 cycles or less, 150 cycles or less, 125 cycles or less, 100 cycles or less, 90 cycles or less, 80 cycles or less, or 70 cycles or less. Combinations of the above ranges are also possible (eg, greater than or equal to 60 cycles, less than or equal to 1000 cycles). Other ranges are also possible.

[0086] In some embodiments, the electrolyte comprises a solvent. In one set of embodiments, the solvent comprises at least one fluorinated organic solvent. In some embodiments, the fluorinated organic solvent and / or mixture of fluorinated organic solvents are used as the only solvent in the electrolyte. In some embodiments, the fluorinated organic solvent and / or mixture of fluorinated organic solvents, upon exposure for a period of time during charge and discharge cycles, results in the formation of a solid electrolyte interface layer that includes a relatively high loading of inorganic materials (e.g., LiF, Li2CO3, Li2O, etc.). In some embodiments, a non-fluorinated solvent may be present.

[0087] In some embodiments, the at least one fluorinated organic solvent is selected from the group of cyclic and linear fluorinated carbonates, fluorinated ethers, and fluorinated esters (e.g., fluorinated alkyl esters).For example, in one embodiment, the solvent comprises at least one fluorinated organic solvent selected from fluoroethylene carbonate and / or difluoroethylene carbonate.Further non-limiting examples of fluorinated organic solvents include, but are not limited to, methyl, 2,2,2,-trifluoroethyl carbonate, 1,1,2,2,-tetrafluoroethyl 2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroacetate, and ethyl trifluoroacetate.

[0088] The fluorinated organic solvent may be present in the electrolyte in any of a variety of suitable amounts. In some embodiments, the fluorinated organic solvent (e.g., fluoroethylene carbonate (FEC)) may be present in an amount of 10 wt% or more, 11 wt% or more, 12 wt% or more, 13 wt% or more, 14 wt% or more, 15 wt% or more, 17 wt% or more, 20 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 88 wt% or more, based on the total weight of the electrolyte. In some embodiments, the fluorinated organic solvent may be present in an amount of 90 wt% or less, 88 wt% or less, 80 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, 20 wt% or less, 17 wt% or less, 15 wt% or less, 13 wt% or less, 12 wt% or less, or 11 wt% or less, based on the total weight of the electrolyte. Combinations of the above ranges are possible (eg, 10% or more and 90% or less by weight, 14% or more and 88% or more and 17% or more and 44% or less by weight). Other ranges are also possible.

[0089] In some embodiments, the solvent further comprises at least one non-fluorinated organic solvent. In some embodiments, the non-fluorinated solvent (or its decomposition products), upon exposure for a period of time during charge and discharge cycles, results in the formation of one or more inorganic materials (e.g., Li2CO3, Li2O) in the solid electrolyte interfacial layer. In some embodiments, the at least one non-fluorinated organic solvent comprises an ester-based solvent. In some embodiments, the organic solvent may comprise one or more of esters of carboxylic acids, esters of phosphoric acids, linear and cyclic ethers and acetals, esters of sulfuric acids, esters of sulfonic acids, esters formed from carboxylic acids and halogenated alcohols, and alkyl esters.

[0090] In some embodiments, the at least one non-fluorinated organic solvent comprises a cyclic and / or linear carbonate. In some such embodiments, the non-fluorinated solvent may comprise one or more carbonate-based solvents selected from the group consisting of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, and ethylene carbonate. Additionally or alternatively, the at least one non-fluorinated organic solvent may comprise an acetate (e.g., methyl acetate, ethyl acetate), an alkyl ester (e.g., ethyl butyrate), a lactone (e.g., γ-butyrolactone), or the like.

[0091] The non-fluorinated organic solvent may be present in the electrolyte in any of a variety of suitable amounts. In some embodiments, the non-fluorinated organic solvent may be present in an amount of 0 wt% or more, 5 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 50 wt% or more, 60 wt% or more, or 70 wt% or more of the total weight of the electrolyte. In some embodiments, the non-fluorinated organic solvent may be present in an amount of 75 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, 30 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, or 5 wt% or less of the total weight of the electrolyte. Combinations of the above ranges are also possible (e.g., 0 wt% or more and 75 wt% or less). Other ranges are also possible.

[0092] The electrolyte solvent may include a fluorinated organic solvent and a non-fluorinated organic solvent in any of a variety of suitable weight ratios. In some embodiments, the weight ratio of fluorinated organic solvent (such as, for example, fluoroethylene carbonate) to non-fluorinated organic solvent may be, in some cases, 1:10 or more, 1:8 or more, 1:5 or more, 1:4 or more, 1:3 or more, 1:2 or more, 1:1 or more, 2:1 or more, 3:1 or more, 5:1 or more, 10:1 or more, 30:1 or more, 50:1 or more, 70:1 or more, or 90:1 or more. In some embodiments, the weight ratio of fluorinated organic solvent to non-fluorinated organic solvent is 100:1 (e.g., 99:1) or less, 90:1 or less, 70:1 or less, 50:1 or less, 30:1 or less, 10:1 or less, 5:1 or less, 3:1 or less, 2:1 or less, 1:1 or less, 1:2 or less, 1:3 or less, 1:4 or less, 1:5 or less, 1:8 or less, 1:10 or less, or 1:15 or less. Combinations of the above ranges are also possible (e.g., 1:10 or more and 100:1 or less, 1:10 or more and 2:1 or less, 1:4 or more and 1:1 or less, or 1:3 or more and 1:1 or less). Other ranges are also possible.

[0093] Further non-limiting examples of useful electrolytes include, but are not limited to, N-methylacetamide, acetonitrile, acetals, ketals, esters (e.g., esters of carbonic acid), carbonates (e.g., dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate), sulfones, sulfites, sulfolane, sulfonimides (e.g., bis(trifluoromethane)sulfonimide lithium salt), aliphatic ethers, acyclic ethers, cyclic ethers, glymes, polyethers, phosphate esters (e.g., hexafluorophosphate), siloxanes, dioxolanes, N-alkylpyrrolidones, nitrate-containing compounds, substituted forms of the foregoing, and blends thereof. Examples of acyclic ethers that can be used include, but are not limited to, diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, trimethoxymethane, 1,2-dimethoxyethane, diethoxyethane, 1,2-dimethoxypropane, and 1,3-dimethoxypropane. Examples of cyclic ethers that can be used include, but are not limited to, tetrahydrofuran, tetrahydropyran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, trioxane, and the like. Examples of polyethers that can be used include, but are not limited to, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), higher glymes, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, and butylene glycol ether. Examples of sulfones that can be used include, but are not limited to, sulfolane, 3-methylsulfolane, 3-sulfolene, and the like. Fluorinated derivatives of the foregoing are also useful as liquid electrolyte solvents.

[0094] In one set of embodiments, the solvent comprises a mixture of fluoroethylene carbonate (FEC) and a non-fluorinated carbonate solvent (e.g., dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or a combination thereof). In some such embodiments, the weight ratio of fluoroethylene carbonate to non-fluorinated carbonate solvent in the organic solvent may be, in some cases, 1:10 or more (e.g., 1:9), 1:8 or more, 1:5 or more, 1:4 or more, 1:3 or more, 1:2 or more, or 1:1 or more. In some embodiments, the weight ratio of fluoroethylene carbonate to non-fluorinated carbonate solvent may be 2:1 or less, 1:1 or less, 1:2 or less, 1:3 or less, 1:4 or less, 1:5 or less, or 1:8 or less. Combinations of the above ranges are also possible (1:10 or more and 2:1 or less, or 1:4 or more and 1:1 or less, or 1:3 or more and 1:1 or less). Other ranges are also possible. In some embodiments, the weight ratio of fluorinated solvent (eg, FEC) to non-fluorinated solvent (eg, DMC) is from 1:4 to 1:1.

[0095] In some embodiments, the electrolyte comprises at least one passivation agent. In some embodiments, the passivation agent can form a passivation layer on the electrode (e.g., an anode such as a lithium metal electrode, and / or a cathode such as a lithium intercalation electrode). In some such embodiments, the resulting passivation layer is part of the solid electrolyte interfacial layer described herein. In some embodiments, an electrochemical cell comprising a solid electrolyte interfacial layer formed in the presence of a passivation agent has the potential to exhibit improved physical properties (e.g., anode stability, cycle life, discharge resistance and discharge capacity) compared to an all-other-factor equal cell comprising a solid electrolyte interfacial layer formed in the absence of a passivation agent.

[0096] For example, in some embodiments, electrochemical cells including a solid electrolyte interface layer (e.g., comprising one or more of LiF, Li2CO3, Li2O, etc.) formed in the presence of a passivation agent exhibit improved physical properties as compared to an otherwise comparable cell including a solid electrolyte interface layer in the absence of a passivation agent. In some embodiments, an electrochemical cell including a solid electrolyte interface layer described herein (e.g., comprising one or more of LiF, Li2CO3, Li2O, etc.) formed in the presence of a passivation agent exhibits a cycle life that is at least 2 times, at least 3 times, at least 5 times, at least 10 times, at least 15 times, at least 20 times, at least 25 times, at least 30 times, at least 40 times, at least 50 times, at least 100 times, at least 200 times, at least 300 times, or at least 400 times that of an otherwise comparable electrochemical cell including a solid electrolyte interface layer but without a passivation agent. In some embodiments, an electrochemical cell including a solid electrolyte interface layer formed in the presence of a passivator exhibits a cycle life that is 500 times or less, 400 times or less, 300 times or less, 200 times or less, 100 times or less, 50 times or less, 40 times or less, 30 times or less, 20 times or less, 10 times or less, or 3 times or less than the cycle life of an otherwise comparable electrochemical cell including a solid electrolyte interface layer but formed in the absence of a passivator. Combinations of the above ranges are also possible (e.g., 2 times or more and 500 times or less). Other ranges are also possible.

[0097] Suitable passivation agents include, but are not limited to, boron-containing compounds, such as compounds containing (oxalato)borate groups. The (oxalato)borate groups may include, for example, bis(oxalato)borate anions and / or difluoro(oxalato)borate anions. According to some embodiments, the passivation agent may include a salt (e.g., an oxalate salt). In some embodiments, the passivation agent including a salt may include a lithium cation. For example, the lithium salt may include lithium bis(oxalato)borate (LiBOB) and / or lithium difluoro(oxalato)borate (LiDFOB). In some embodiments, the lithium salt may include lithium tetrafluoroborate (LiBF4).

[0098] In some embodiments, the total weight of passivation agents (e.g., (oxalato)borate groups such as lithium bis(oxalato)borate (LiBOB) and / or lithium difluoro(oxalato)borate) in the electrochemical cell can be about 30% by weight or less, about 28% by weight or less, about 25% by weight or less, about 22% by weight or less, about 20% by weight or less, about 18% by weight or less, about 15% by weight or less, about 12% by weight or less, about 10% by weight or less, about 8% by weight or less, about 6% by weight or less, about 5% by weight or less, about 4% by weight or less, about 3% by weight or less, about 2% by weight or less, or about 1% by weight or less, based on the total weight of the electrolyte. In some embodiments, the total weight of the passivation agent in the electrochemical cell is greater than about 0.2 wt%, greater than about 0.5 wt%, greater than about 1 wt%, greater than about 2 wt%, greater than about 3 wt%, greater than about 4 wt%, greater than about 6 wt%, greater than about 8 wt%, greater than about 10 wt%, greater than about 15 wt%, greater than about 18 wt%, greater than about 20 wt%, greater than about 22 wt%, greater than about 25 wt%, or greater than about 28 wt%, based on the total weight of the electrolyte. Combinations of the above ranges are also possible (e.g., between about 0.2 wt% and about 30 wt%, between about 0.2 wt% and about 20 wt%, between about 0.5 wt% and about 20 wt%, between about 1 wt% and about 8 wt%, between about 1 wt% and about 6 wt%, between about 4 wt% and about 10 wt%, between about 6 wt% and about 15 wt%, or between about 8 wt% and about 20 wt%). Other ranges are also possible.

[0099] In some embodiments, an electrochemical cell may include two or more passivation agents that can interact synergistically to enhance one or more properties of the electrochemical cell beyond what would be expected from the effect of any one passivation agent individually on the electrochemical cell.

[0100] Further examples of passivating agents include, but are not limited to, sultones (e.g., 1,3 propane sultone (PS), prop-1-ene-1,3-sultone (PES)), sulfonates (e.g., methylene methane sulfonate (MMDS)), vinylene carbonate, phosphites, lithium salts (e.g., LiBF4), xanthate groups (e.g., lithium xanthate, potassium xanthate, lithium ethyl xanthate, potassium ethyl xanthate, lithium isobutyl xanthate, potassium isobutyl xanthate, lithium tert-butyl xanthate, potassium tert-butyl xanthate), polyxanthate groups, carbamate groups (e.g., lithium dithiocarbamate, potassium dithiocarbamate, lithium diethyldithiocarbamate, and potassium diethyldithiocarbamate), polycarbamate groups, N-O groups (e.g., lithium nitrate, magnesium nitrate), silanes, and the like. Further examples of passivation agents and methods of use thereof are described in detail, for example, in U.S. Patent Application Publication No. 2018-0351158, the entirety of which is incorporated herein by reference.

[0101] In some embodiments, the electrolyte includes at least one lithium salt. In one set of embodiments, the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). Further examples of lithium include LiSCN, LiBr, LiI, LiSO3CH3, LiNO3, LiPF6, LiBF4, LiB(Ph)4, LiClO4, LiAsF6, Li2SiF6, LiSbF6, LiAlCl4, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, salts containing the tris(oxalato)phosphate anion (such as, but not limited to, lithium tris(oxalato)phosphate), LiC(SO2CF3)3, LiCF3SO3, LiN(SO2F)2, LiN(SO2CF3)2, LiC(C n F 2n+1 SO2)3 (n is an integer ranging from 1 to 20), and (C n F 2n+1 SO2) m XLi, where n is an integer ranging from 1 to 20, m is 1 when X is selected from oxygen or sulfur, m is 2 when X is selected from nitrogen or phosphorus, and m is 3 when X is selected from carbon or silicon. Other electrolyte salts that may be useful include lithium polysulfides (LiSx), and lithium salts of organic polysulfides (LiSxR). n where x is an integer from 1 to 20, n is an integer from 1 to 3, and R is an organic group, including those disclosed in U.S. Pat. No. 5,538,812 to Lee et al., which is incorporated herein by reference in its entirety for all purposes.

[0102] When present, the lithium salt may be present in the electrolyte at various suitable concentrations. In some embodiments, the lithium salt is present in the electrolyte at a concentration of 0.01M or more, 0.02M or more, 0.05M or more, 0.1M or more, 0.2M or more, 0.5M or more, 1M or more, 2M or more, or 5M or more. The lithium salt may be present in the electrolyte at a concentration of 10M or less, 5M or less, 2M or less, 1M or less, 0.5M or less, 0.2M or less, 0.1M or less, 0.05M or less, or 0.02M or less. Combinations of the above ranges are also possible (e.g., 0.01M or more and 10M or less, or 0.01M or more and 5M or less). Other ranges are also possible.

[0103] In some embodiments, the electrolyte comprises one or more room temperature ionic liquids. Room temperature ionic liquids, when present, typically comprise one or more cations and one or more anions. Non-limiting examples of suitable cations include lithium cations and / or one or more quaternary ammonium cations, such as imidazolium cations, pyrrolidinium cations, pyridinium cations, tetraalkylammonium cations, pyrazolium cations, piperidinium cations, pyridazinium cations, pyrimidinium cations, pyrazinium cations, oxazolium cations, and trizolium cations. Non-limiting examples of suitable anions include trifluoromethylsulfonate (CF3SO3 - ), bis(fluorosulfonyl)imide (N(FSO2)2 - ), bis(trifluoromethylsulfonyl)imide ((CF3SO2)2N - ), bis(perfluoroethylsulfonyl)imide ((CF3CF2SO2)2N - ) and tris(trifluoromethylsulfonyl)methide ((CF3SO2)3C -). Non-limiting examples of suitable ionic liquids include N-methyl-N-propylpyrrolidinium / bis(fluorosulfonyl)imide and 1,2-dimethyl-3-propylimidazolium / bis(trifluoromethanesulfonyl)imide. In some embodiments, the electrolyte comprises both a room temperature ionic liquid and a lithium salt. In other embodiments, the electrolyte comprises a room temperature ionic liquid and does not comprise a lithium salt.

[0104] Suitable active electrode materials for use in the first electrode (e.g., as the anode active electrode species in the anode of an electrochemical cell described herein) include, but are not limited to, lithium metal, such as lithium foil or lithium deposited on a substrate, lithium alloys (e.g., lithium-aluminum alloys and lithium-tin alloys). The lithium may be contained as a film or as multiple films, optionally separated by a protective material, such as a ceramic material or an ionically conductive material described herein. Suitable ceramic materials include silica, alumina, and / or lithium-containing glassy materials, such as lithium phosphate, lithium aluminate, lithium silicate, lithium carbonate, lithium oxide, lithium phosphate oxynitride, lithium tantalum oxide, lithium aluminosulfide, lithium titanate oxide, lithium silcosulfide, lithium germanosulfide, lithium aluminosulfide, lithium borosulfide, lithium phosphosulfide, and combinations of two or more of the foregoing. Lithium alloys suitable for use in the embodiments described herein include alloys of lithium with aluminum, magnesium, silicium, indium, silver, and / or tin. In some embodiments, these materials are preferred, although other cell chemistries are contemplated. In some embodiments, the first electrode may include one or more binder materials (e.g., polymers, etc.).

[0105] In some embodiments, the thickness of the first electrode (e.g., anode) may vary, for example, from about 1 to about 200 μm. For example, the first electrode (e.g., anode) may have a thickness of less than about 200 μm, less than about 100 μm, less than about 50 μm, less than about 25 μm, less than about 10 μm, or less than about 5 μm. In some embodiments, the first electrode (e.g., anode) may have a thickness of about 1 μm or more, about 5 μm or more, about 10 μm or more, about 25 μm or more, about 50 μm or more, about 100 μm or more, or about 150 μm or more. Combinations of the above ranges are also possible (e.g., between about 1 μm and about 200 μm, between about 1 μm and about 100 μm, between about 5 μm and about 50 μm, between about 5 μm and about 25 μm, or between about 10 μm and about 25 μm). Other ranges are also possible. The thickness selection may depend on cell design parameters such as the desired lithium excess, cycle life, and thickness of the second electrode.

[0106] Methods for depositing the negative electrode material (e.g., an alkali metal anode such as lithium) onto a substrate include thermal evaporation, sputtering, jet deposition, laser ablation, etc. Alternatively, when the anode comprises lithium foil, or lithium foil and a substrate, they may be laminated together by lamination methods known in the art to form the anode.

[0107] In some embodiments, the electroactive material in the second electrode (e.g., the cathode active electrode species in the cathode of an electrochemical cell described herein) may comprise a metal oxide. In some embodiments, an intercalation electrode (e.g., a lithium intercalation cathode, also referred to herein as a lithium ion intercalation cathode) may be used (e.g., as the second electrode). Non-limiting examples of suitable materials capable of intercalating ions of the electroactive material (e.g., alkali metal ions) include oxides, titanium sulfide, and iron sulfide. In some embodiments, the second electrode (e.g., cathode) may comprise an intercalation electrode comprising a lithium transition metal oxide or a lithium transition metal phosphate. Further examples include Li x CoO2 (also referred to herein as lithium cobalt oxide; e.g., Li 1.1 CoO2), Li x NiO2, Li x MnO2, Li x Mn2O4 (e.g., Li 1.05 Mn2O4), Li x CoPO4, Li x MnPO4, LiCo x Ni (1-x) O2, and LiCo x Ni y Mn (1-x-y) O2, Li 1.05 Mn2O4), Li x CoPO4, Li x MnPO4, LiCo x Ni (1-x) O2, and LiCo x Ni y Mn (1-x-y) O2 (also referred to herein as lithium-nickel-manganese-cobalt oxide; e.g., LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 3 / 5 Mn 1.5 Co 1.5 O2, LiNi 4 / 5 Mn 1 / 10 Co 1 / 10 O2, LiNi1 / 2 Mn3 / 10 Co 1.5 X (e.g., Li, O, as described elsewhere herein) x M y O z For intercalation cathodes having an x-column structure, where M is a metal or combination of metals, x may be 0 or greater and 2 or less. X is typically 1 or greater and 2 or less when the electrochemical cell is fully discharged and less than 1 when the electrochemical cell is fully charged. In some embodiments, a fully charged electrochemical cell may have a value of x that is 1 or greater and 1.05 or less, 1 or greater and 1.1 or less, or 1 or greater and 1.2 or less. As further examples, x-column structures such as (0 <x≦1)であるLi x NiPO4, (x+y=2) LiMn x Ni y O4 (e.g., LiMn 1.5 Ni 0.5 O4), (x+y+z=1) LiNi x C y Al z O2, LiFePO4, and combinations thereof. In some embodiments, the electroactive material in the cathode comprises a lithium transition metal phosphate (e.g., LiFePO4), which in some embodiments can be substituted with a borate and / or a silicate.

[0108] In some embodiments, the electroactive material in the second electrode (e.g., the cathode active electrode species in the cathode of the electrochemical cells described herein) may include electroactive transition metal chalcogenides, electroactive conductive polymers, and / or electroactive sulfur-containing materials, and combinations thereof. As used herein, the term "chalcogenide" refers to a compound that includes one or more of the elements oxygen, sulfur, and selenium. Examples of suitable transition metal chalcogenides include, but are not limited to, electroactive oxides, sulfides, and selenides of transition metals selected from the group consisting of Mn, V, Cr, Ti, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Hf, Ta, W, Re, Os, and Ir. In one embodiment, the transition metal chalcogenide is selected from the group consisting of electroactive oxides of nickel, manganese, cobalt, and vanadium, and electroactive sulfides of iron. In one embodiment, the cathode comprises one or more of the following materials: manganese dioxide, iodine, silver chromate, silver oxide and vanadium pentoxide, copper oxide, copper oxyphosphate, lead sulfide, iron sulfide, lead bismuthate, bismuth trioxide, cobalt dioxide, copper chloride, manganese dioxide, and carbon. In another embodiment, the cathode active layer comprises an electroactive conductive polymer. Examples of suitable electroactive conductive polymers include, but are not limited to, electroactive and electronically conductive polymers selected from the group consisting of polypyrrole, polyaniline, polyphenylene, polythiophene, and polyacetylene. In some embodiments, it is desirable to use polypyrroles, polyanilines, and polyacetylenes as the conductive polymer.

[0109] According to some embodiments, a variety of cathode active materials are suitable for use in the cathodes of the electrochemical cells described herein. In some embodiments, the cathode active material includes a lithium intercalation compound (e.g., a compound that can reversibly insert lithium ions into lattice and / or interstitial sites). In some cases, the cathode active material includes a layered oxide. A layered oxide generally refers to an oxide having a lamellar structure (e.g., multiple sheets or layers stacked together). Non-limiting examples of suitable layered oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and lithium manganese oxide (LiMnO2). In some embodiments, the layered oxide is lithium nickel manganese cobalt oxide (LiNi x Mn y Co z O2, also referred to as "NMC" or "NCM". For example, a non-limiting example of a suitable NMC compound is LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), and Li 1+X (Ni 0.85 Co 0.10 Mn 0.05 ) 1-X O2 (NCM851005), where x is about 0.01. In some embodiments, the layered oxide has the formula (Li2MnO3)x(LiMO2) (1-X) where M is one or more of Ni, Mn, and Co. For example, the layered oxide can have the formula: (Li2MnO3) 0.25 (LiNi 0.3 Co 0.15 Mn 0.55 O2) 0.75 may be also possible.

[0110] In some embodiments, the layered oxide is lithium nickel cobalt aluminum oxide (LiNi X Co y Al z O2, also referred to as "NCA"). For example, a non-limiting example of a suitable NCA compound is LiNi 0.8 Co 0.15 Al 0.05 It's O2.

[0111] In some embodiments, the cathode active material comprises a transition metal polyanion oxide (e.g., a compound that includes a transition metal, oxygen, and / or an anion having an absolute charge greater than one). A non-limiting example of a suitable transition metal polyanion oxide is lithium iron phosphate (LiFePO4, also known as "LFP"). Another non-limiting example of a suitable transition metal polyanion oxide is lithium manganese iron phosphate (LiMn x Fe 1-x PO4, also referred to as "LMFP"). A non-limiting example of a suitable LMFP compound is LiMn 0.8 Fe 0.2 PO4. In some embodiments, the cathode active material comprises a spinel (e.g., a compound having the structure AB2O4, where A can be Li, Mg, Fe, Mn, Zn, Cu, Ni, Ti, or Si, and B can be Al, Fe, Cr, Mn, or V). A non-limiting example of a suitable spinel is lithium manganese oxide (LiMn2O4, also known as "LMO"). Another non-limiting example is lithium manganese nickel oxide (LiNi x M 2-x O4, also referred to as "LMNO"). A non-limiting example of a suitable LMNO compound is LiNi 0.5 Mn 1.5 O4. In some cases, the electroactive material is Li 1.14 Mn 0.42 Ni 0.25 Co 0.29O2 ("HC-MNC"), lithium carbonate (Li2CO3), lithium carbides (e.g., Li2C2, Li4C, Li6C2, Li8C3, Li6C3, Li4C3, Li4C5), vanadium oxides (e.g., V2O5, V2O3, V6O 13 ), and / or vanadium phosphate (e.g., lithium vanadium phosphate such as Li3V2(PO4)3), or any combination thereof.

[0112] In some embodiments, the cathode active material includes a conversion compound. For example, the cathode may be a lithium conversion cathode. It is recognized that cathodes including a conversion compound can have a relatively large specific capacity. Without wishing to be bound by a particular theory, a relatively large specific capacity can be achieved by utilizing all possible oxidation states of the compound through a conversion reaction in which multiple electron transfers occur per transition metal (e.g., compared to 0.1 to 1 electron transfer in intercalation compounds). Suitable conversion compounds include, but are not limited to, transition metal oxides (e.g., Co3O4), transition metal hydrides, transition metal sulfides, transition metal nitrides, and transition metal fluorides (e.g., CuF2, FeF2, FeF3). Transition metals generally refer to elements whose atoms have a partially filled d-subshell (e.g., Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Rf, Db, Sg, Bh, Hs).

[0113] The electrodes described herein may be part of an electrochemical cell that is incorporated into a battery (e.g., a rechargeable battery). In some embodiments, an electrochemical cell (including one or more electrodes described herein) may be used to power or otherwise be incorporated into an electric vehicle. As a non-limiting example, the electrochemical cells described herein may be used to power the drivetrain of an electric vehicle in some cases. The vehicle may be any suitable vehicle adapted for travel on land, sea, and / or air. For example, the vehicle may be a car, a truck, a motorcycle, a boat, a helicopter, an airplane, and / or any other suitable type of vehicle.

[0114] In some embodiments, the electrochemical cells described herein include at least one current collector. For example, referring again to FIG. 1, the electrochemical cell 10 includes a cathode current collector 20 and an anode current collector 22. The material of the current collector may be selected from metals (e.g., copper, nickel, aluminum, passivated metals, and other suitable metals), metallized polymers, conductive polymers, polymers with conductive particles dispersed therein, and other suitable materials in some cases. In some embodiments, the current collector is deposited on the electrode layer using physical vapor deposition, chemical vapor deposition, electrochemical vapor deposition, sputtering, doctor blading, flash deposition, or any other suitable deposition technique for the selected material. In some cases, the current collector is formed separately and bonded to the electrode structure. However, it should be understood that in some embodiments, a current collector separate from the electroactive layer may not be required.

[0115] One set of embodiments described herein relates to the formation of electrode slurries, such as electrode slurries, that maintain fluid-like properties over a period of time between the formation of the slurry and the application (or application) of the slurry to a current collector. These slurries may be easier to process (e.g., easier to mix, easier to apply, easier to apply uniformly) than slurries that do not maintain fluid-like properties (e.g., slurries that have at least a portion that has gelled and / or solidified). The slurries may include a particulate electroactive material and a solvent. In some embodiments, the slurries may further include a binder and / or one or more additives. The particulate electroactive material in the slurry may have one or more characteristics that tend to promote gelation (e.g., may have a small average particle size, may contain a certain amount of nickel), but may still be a component of the slurry that has fluid-like properties. In some embodiments, one or more reactive groups (e.g., -OH groups, -COOH groups) present on the surface of the particulate electroactive material may be passivated (e.g., by exposure to a second passivating agent as described herein, by exposure to a silane compound) prior to slurry formation.

[0116] As used herein, a slurry is a material that typically, but not always, includes at least one liquid component and at least one solid component. The solid component may be at least partially suspended in a liquid and / or at least partially dissolved in a liquid.

[0117] As described herein, in some embodiments, the electrochemical cell includes a separator. The separator generally includes a polymeric material (e.g., a polymeric material that swells or does not swell when exposed to an electrolyte). In some embodiments, the separator is located between the electrolyte and an electrode (e.g., between the electrolyte and a first electrode, between the electrolyte and a second electrode, between the electrolyte and an anode, or between the electrolyte and a cathode).

[0118] In some embodiments, the electrochemical cell may further include a separator interposed between the cathode and the anode. The separator may be a solid, non-conductive or insulating material that separates or insulates the anode and cathode from one another to prevent short circuits and allows transport of ions between the anode and cathode. In some embodiments, the porous separator may be permeable to the electrolyte.

[0119] The pores of the separator may be partially or substantially filled with the electrolyte. The separator may be provided as a porous free-standing membrane that is sandwiched between the anode and cathode during cell manufacture. Alternatively, a porous separator layer may be applied directly to the surface of one of the electrodes, as described, for example, in WO 99 / 33125 to Carlson et al. and U.S. Patent No. 5,194,341 to Bagley et al.

[0120] The separator can be made of a variety of materials. In some cases the separator may be made of a polymer, and in some cases the separator may be formed of an inorganic material (e.g., glass fiber filter paper). Examples of suitable separator materials include, but are not limited to, polyolefins (e.g., polyethylene, poly(butene-1), poly(n-pentene-2), polypropylene, polytetrafluoroethylene), polyamines (e.g., poly(ethyleneimine) and polypropyleneimine (PPI)); polyamides (e.g., polyamide(nylon), poly(ε-caprolactam) (nylon 6), poly(hexamethylene adipamide) (nylon 66)); polyimides (e.g., polyimide, polynitrile, polyisoprene ... poly(pyromellitimide-1,4-diphenyl ether) ("Kapton®") ("NOMEX®") ("KEVLAR®"); polyether ether ketone (PEEK); vinyl polymers (e.g., polyacrylamide, poly(2-vinylpyridine), poly(N-vinylpyrrolidone), poly(methyl cyanoacrylate), poly(ethyl cyanoacrylate), poly(butyl cyanoacrylate), poly(isobutyl cyanoacrylate), poly(vinyl acetate), polyvinyl), poly(vinyl alcohol), poly(vinyl chloride), poly(vinyl fluoride), poly(2-vinylpyridine), vinyl polymers, polychlorotrifluoroethylene, and poly(isohexyl cyanoacrylate); polyacetals; polyesters (e.g., polycarbonate, polybutylene terephthalate, polyhydroxybutyrate); polyethers (poly(ethylene oxide) (PEO), poly(propylene oxide) (PPO), poly(tetramethylene oxide) (PTMO)); vinyl lidene polymers (e.g., polyisobutylene, poly(methylstyrene), poly(methyl methacrylate) (PMMA), poly(vinylidene chloride), and poly(vinylidene fluoride)); polyaramids (e.g., poly(imino-1,3-phenyleneiminoisophthaloyl) and poly(imino-1,4-phenyleneiminoterephthaloyl)); polyheteroaromatics (e.g., polybenzimidazole (PBI), polybenzobisoxazole (PBO), and polybenzobisthiazole (PBT));Polyheterocyclic compounds (e.g., polypyrrole); polyurethanes; phenolic polymers (e.g., phenol formaldehyde); polyalkynes (e.g., polyacetylene); polydienes (e.g., 1,2-polybutadiene, cis or trans-1,4-polybutadiene); polysiloxanes (e.g., poly(dimethylsiloxane) (PDMS), poly(diethylsiloxane) (PDES), polydiphenylsiloxane (PDPS), and polymethylphenylsiloxane (PMPS)); and inorganic polymers (e.g., polyphosphazenes, polyphosphonates, polysilanes, polysilazanes). In some embodiments, the polymer may be selected from poly(n-pentene-2), polypropylene, polytetrafluoroethylene, polyamides (e.g., polyamide (nylon), poly(ε-caprolactam) (nylon 6), poly(hexamethylene adipamide) (nylon 66), polyamides (e.g., polynitrile, and poly(pyromellitimide-1,4-diphenyl ether) ("Kapton®") ("NOMEX®") ("KEVLAR®")), polyether ether ketone (PEEK), and combinations thereof;

[0121] The separator may be coated with various materials (e.g., ceramics). In some embodiments, the separator is a ceramic-coated separator. Non-limiting examples of ceramics include alumina, boehmite, and / or silica. In some embodiments, separators comprising the aforementioned polymeric materials (e.g., polyolefins) may be coated with a ceramic as described herein.

[0122] Liquid electrolyte solvents are also useful as plasticizers for gel polymer electrolytes, i.e., electrolytes that include one or more polymers that form a semi-solid network. Examples of useful gel polymer electrolytes include, but are not limited to, those that include one or more polymers selected from the group consisting of polyethylene oxide, polypropylene oxide, polyacrylonitrile, polysiloxane, polyimide, polyphosphazene, polyether, sulfonated polyimide, perfluorinated membrane (NAFION resin), polydivinyl polyethylene glycol, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polysulfone, polyethersulfone, derivatives thereof, copolymers thereof, crosslinked and network structures thereof, and blends thereof, and optionally one or more plasticizers. In some embodiments, the gel polymer electrolyte includes 10-20% by volume, 20-40% by volume, 60-70% by volume, 70-80% by volume, 80-90% by volume, or 90-95% by volume of a heterogeneous electrolyte.

[0123] In some embodiments, one or more solid polymers may be used to form the electrolyte. Examples of useful solid polymer electrolytes include, but are not limited to, those that include one or more polymers selected from the group consisting of polyethers, polyethylene oxides, polypropylene oxides, polyimides, polyphosphazenes, polyacrylonitriles, polysiloxanes, derivatives thereof, copolymers thereof, crosslinked and network structures thereof, and blends thereof.

[0124] In addition to electrolyte solvents, gelling agents, and polymers known in the art to form an electrolyte, the electrolyte may further include one or more ionic electrolyte salts, also known in the art, to enhance ionic conductivity.

[0125] According to some embodiments, it may be advantageous to apply an anisotropic force to the electrochemical cells described herein during charging and / or discharging. In some embodiments, the electrochemical cells and / or electrodes described herein may be configured to withstand an applied anisotropic force (e.g., a force applied to reinforce the morphology of the electrodes within the cell) while maintaining their structural integrity.

[0126] In some embodiments, any of the electrodes described herein may be part of an electrochemical cell constructed and arranged such that an anisotropic force having a component perpendicular to a surface (e.g., active surface) of an electrode (e.g., an anode comprising lithium metal and / or lithium alloy) in the electrochemical cell is applied to the cell during at least one period during charging and / or discharging of the cell. In one set of embodiments, the applied anisotropic force may be selected to enhance the morphology of the electrode (e.g., the anode, such as a lithium metal and / or lithium alloy anode).

[0127] "Anisotropic force" has its usual meaning in the art, meaning a force that is unequal in all directions. An example of a force that is equal in all directions is an internal pressure within a fluid or substance, such as an internal gas pressure of an object. An example of a force that is unequal in all directions is a force that is directed in a particular direction, such as the force that an object on a table exerts on the table via gravity. Another example of an anisotropic force is a force exerted by a band placed around an object. For example, a rubber band or a turnbuckle can exert a force around the object that it is wrapped around. However, the band should not exert a force directly on any part of the outer surface of the object that is not in contact with the band. Furthermore, if the band is stretched along a first axis more than along a second axis, the band can exert a greater force in a direction parallel to the first axis than a force applied parallel to the second axis.

[0128] In such a case, the anisotropic force includes a component perpendicular to the surface (e.g., active surface) of the electrode in the electrochemical cell. In this specification, the term "active surface" is used to refer to the surface of the electrode where an electrochemical reaction can occur. A force with a "normal component" to the surface is given its usual meaning as understood by a person skilled in the art, including, for example, a force that acts at least in part in a direction substantially perpendicular to the surface. For example, if an object rests on a horizontal table and is only influenced by gravity, the object exerts a force in a direction substantially completely perpendicular to the surface of the table. If the object is also biased laterally across the surface of the horizontal table, the object exerts a force on the table that is not completely perpendicular to the horizontal surface, but includes a component perpendicular to the surface of the table. A person skilled in the art will understand other examples of these terms, especially as they apply in the description herein. In the case of a curved surface (e.g., concave or convex), the component of the anisotropic force perpendicular to the surface (e.g., active surface) of the electrode can correspond to a component perpendicular to a plane tangent to the curved surface at the point where the anisotropic force is applied. The anisotropic force may be applied at one or more predetermined locations, optionally distributed randomly on the surface (e.g., active surface) of the anode. In some embodiments, the anisotropic force is applied uniformly on the surface (e.g., active surface) of the first electrode (e.g., of the anode).

[0129] Any of the properties and / or performance metrics of an electrochemical cell described herein may be achieved, alone or in combination with one another, during the application of an anisotropic force to the electrochemical cell during charging and / or discharging (e.g., during charging and / or discharging of the cell). In some embodiments, the anisotropic force applied to an electrode, to an electrochemical cell (e.g., during at least one period during charging and / or discharging of the cell) may include a component perpendicular to a surface (e.g., an active surface) of the electrode (e.g., an anode, such as a lithium metal and / or lithium alloy anode in an electrochemical cell).

[0130] As described herein, in some embodiments, the surface of the anode may be strengthened during cycling (e.g., in the case of lithium, the occurrence of a mossy or rough surface of lithium may be reduced or eliminated) by application of an externally applied (in some embodiments, uniaxial) pressure. The externally applied pressure may in some embodiments be selected to be greater than the yield stress of the material forming the anode. For example, in the case of an anode comprising lithium, the cell may be subjected to a pressure of at least about 8 kgf / cm. 2 , at least about 9kgf / cm 2 , at least about 10 kgf / cm 2 , at least about 20kgf / cm 2 , at least about 30kgf / cm 2 , at least about 40kgf / cm 2 , or at least about 50 kgf / cm 2 This is because the yield stress of lithium is about 7-8 kgf / cm 2 Therefore, at pressures greater than this value (e.g., uniaxial pressure), the mossy Li, or surface roughness, may be reduced or suppressed at all. The surface roughness of lithium may mimic the surface pressing against it. Thus, at least about 8 kgf / cm 2 , at least about 9kgf / cm 2 , at least about 10 kgf / cm 2 , at least about 20kgf / cm 2 , at least about 30kgf / cm 2 , at least about 40kgf / cm 2 , or at least about 50 kgf / cm 2 When cycling under an externally applied pressure, if the pressing surface is smooth, the lithium surface may become smoother with cycling. As described herein, the pressing surface can be modified by selecting an appropriate material disposed between the cathode and anode.

[0131] As described herein, the anisotropic force applied during charging and / or discharging may be applied using any method known in the art. In some embodiments, the force may be applied using a compression spring. The force may be applied using other elements (either inside or outside the containment structure), including, but not limited to, Belleville washers, machine screws, pneumatic devices, and / or weights. In some cases, the cells are pre-compressed before being inserted into the containment structure, and expand upon insertion into the containment structure to generate a net force on the cells. Suitable methods for applying such forces are described in detail, for example, in U.S. Pat. No. 9,105,938, which is incorporated herein by reference in its entirety.

[0132] In some embodiments, the electrochemical cells described herein are designed to include a second electrode having an electroactive material (e.g., a cathode active electrode species in the cathode of the electrochemical cells described herein) that has a moderate voltage relative to lithium metal. The voltage of the electroactive material relative to lithium metal can be measured by first cycling the electrochemical cell containing the electroactive material and lithium metal at a rate of C / 5 at least four times (e.g., 5, 6, 8, 10 times), then discharging the electrochemical cell at a rate of C / 5 and measuring the voltage as the cell discharges. The average voltage measured over the discharge process is then determined, and this value is considered to be the voltage relative to lithium metal. In some embodiments, the electroactive material in the second electrode has a voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, or 4.4V or more. 2V or more, or 4.4V or more. In some embodiments, the electroactive material in the second electrode has a voltage relative to lithium metal of 4.5 V or less, 4.2 V or less, 4.0 V or less, 3.8 V or less, 3.6 V or less, 3.4 V or less, 3.2 V or less, or 3 V or less. Combinations of the above ranges are also possible (e.g., 2.8 V or more and 4.5 V or less). Other ranges are also possible.

[0133] In some embodiments, the electrochemical cells described herein are designed to include a second electrode having an electroactive material (e.g., a cathode active electrode species in the cathode of the electrochemical cells described herein) that has a moderate open circuit voltage relative to lithium metal. The open circuit voltage of the electroactive material relative to lithium metal may be measured by determining the open circuit voltage when a battery containing the electroactive material and lithium metal is charged to half its capacity. This may be accomplished by first determining the capacity of the battery by cycling the battery. The battery may then be charged to half its measured capacity and allowed to rest for 2 minutes. After these steps, the open circuit voltage may be measured. In some embodiments, the electroactive material in the second electrode has an open circuit voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, or 4.4V or more. In some embodiments, the electroactive material in the second electrode has an open circuit voltage vs. lithium metal of 4.5 V or less, 4.2 V or less, 4.0 V or less, 3.8 V or less, 3.6 V or less, 3.4 V or less, 3.2 V or less, or 3 V or less. Combinations of the above ranges are also possible (e.g., 2.8 V or more and 4.5 V or less). Other ranges are also possible.

[0134] Properties of the electroactive material (e.g., for the second electrode) other than their voltage and open circuit voltage with respect to lithium may also be relevant in some embodiments. For example, in some embodiments, an electrochemical cell may include a second electrode that includes an electroactive material (e.g., a cathode active electrode species in the cathode of an electrochemical cell described herein) that exhibits one or more plateaus (or flat areas) in the value of the voltage with respect to lithium as a function of cycle life during charging and / or discharging, and the value of the plateau may be one or more of the aforementioned values ​​related to the voltage of the material with respect to lithium metal. As used herein, an electroactive material exhibits a plateau (i.e., a plateau voltage) if it exhibits a constant or substantially constant voltage with respect to lithium (e.g., varying by 10% or less, or 5% or less) during at least a portion of the charging and / or discharging procedure. The voltage at which a plateau occurs for an electroactive material (i.e., a plateau voltage) may be determined by employing the same procedure used to determine the voltage of an electroactive material with respect to lithium metal, assessing whether regions consistent with a plateau are observed, and, if so, determining the average voltage of those regions. In some embodiments, the electroactive material in the second electrode has a plateau voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, 4.4V or more. In some embodiments, the electroactive material in the second electrode has a plateau voltage relative to lithium metal of 4.5V or less, 4.2V or less, 4.0V or less, 3.8V or less, 3.6V or less, 3.4V or less, 3.2V or less, or 3V or less. Combinations of the above ranges are also possible (e.g., 2.8V or more and 4.5V or less). Other ranges are also possible.

[0135] As another example, an electrochemical cell may include a second electrode comprising an electroactive material suitable for charging to less than 5 V, less than 4.5 V, less than 4 V, or less than 3.5 V under normal operating conditions (e.g., charging the second electrode to, for example, greater than 5 V, 4.5 V, 4 V, or 3.5 V, respectively, is typically considered an abuse test, is not recommended by manufacturers, and / or raises safety concerns).

[0136] In some embodiments, one or more voltages (e.g., maximum voltage, minimum voltage, median voltage, mode voltage) measured during the charging and / or discharging process in a cell including a lithium metal electrode may have one or more of the aforementioned values ​​relative to the average voltage. In some embodiments, the electroactive material in the second electrode has a maximum voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, or 4.4V or more. In some embodiments, the electroactive material in the second electrode has a maximum voltage relative to lithium metal of 4.5V or less, 4.2V or less, 4.0V or less, 3.8V or less, 3.6V or less, 3.4V or less, 3.2V or less, or 3V or less. Combinations of the above ranges are also possible (e.g., 2.8V or more and 4.5V or less). Other ranges are also possible.

[0137] In some embodiments, the electroactive material in the second electrode has a minimum voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, 4.4V or more. In some embodiments, the electroactive material in the second electrode has a minimum voltage relative to lithium metal of 4.5V or less, 4.2V or less, 4.0V or less, 3.8V or less, 3.6V or less, 3.4V or less, 3.2V or less, or 3V or less. Combinations of the above ranges are also possible (e.g., 2.8V or more and 4.5V or less). Other ranges are also possible.

[0138] In some embodiments, the electroactive material in the second electrode has a median voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, or 4.4V or more. In some embodiments, the electroactive material in the second electrode has a median voltage relative to lithium metal of 4.5V or less, 4.2V or less, 4.0V or less, 3.8V or less, 3.6V or less, 3.4V or less, 3.2V or less, or 3V or less. Combinations of the above ranges are also possible (e.g., 2.8V or more and 4.5V or less). Other ranges are also possible.

[0139] In some embodiments, the electroactive material in the second electrode has a modal voltage relative to lithium metal of 2.8V or more, 3V or more, 3.2V or more, 3.4V or more, 3.6V or more, 3.8V or more, 4.0V or more, 4.2V or more, or 4.4V or more. In some embodiments, the electroactive material in the second electrode has a modal voltage relative to lithium metal of 4.5V or less, 4.2V or less, 4.0V or less, 3.8V or less, 3.6V or less, 3.4V or less, 3.2V or less, or 3V or less. Combinations of the above ranges are also possible (e.g., 2.8V or more and 4.5V or less). Other ranges are also possible.

[0140] In some embodiments, additional layers may be present in the electrochemical cells described herein. In some implementations, one or more intervening layers (e.g., ionically conductive layers) may be present between the anode 12 and the electrolyte 14 of FIG. 1. In one set of embodiments, the ionically conductive layer (e.g., a single-ion conductive layer) may have a shape or structure that protects the anode electroactive material layer from one or more undesirable components (in the electrolyte) in the electrochemical cell. In some such embodiments, the anode electroactive material layer may be at least partially encapsulated by the ionically conductive layer.

[0141] In some embodiments, the ionically conductive layer may be formed by any of a variety of suitable methods and may include any of a variety of suitable materials. Some methods involve forming the ionically conductive layer by aerosol deposition methods. Aerosol deposition methods are known in the art and generally involve depositing (e.g., spraying) particles (e.g., inorganic particles, polymeric particles) onto a surface at a relatively high speed. Aerosol deposition as described herein generally results in collision and / or elastic deformation of at least a portion of the plurality of particles. In some embodiments, the aerosol deposition may be carried out under conditions (e.g., with a speed) sufficient to cause fusion of at least a portion of the plurality of particles with at least another portion of the plurality of particles. For example, in some embodiments, the plurality of particles is deposited on the electroactive material (and / or any sublayer disposed thereon) at a relatively high speed such that at least a portion of the plurality of particles fuses (e.g., forms a portion of the protective layer and / or a sublayer (or sublayer) of the protective layer). The rate required for fusing the particles may depend on factors such as the material composition of the particles, the size of the particles, the Young's modulus of the particles, and / or the yield strength of the particles or the material from which the particles are formed.

[0142] In some embodiments, the ion-conducting layer described herein comprises an inorganic material. The inorganic material may comprise a ceramic material (e.g., glass, glass-ceramic material). The inorganic material may be crystalline, amorphous, or partially crystalline and partially amorphous. In some embodiments, the ion-conducting layer comprises LixMPySz. For such inorganic materials, x, y, and z may be integers (e.g., integers less than 32), and / or M may comprise Sn, Ge, and / or Si. As an example, the inorganic material may be Li 22 SiP2S 18 , Li 24 MP2S 19 (For example, Li 24 SiP2S 19 ), LiMP2S 12(e.g., M=Sn, Ge, Si), and / or LiSiPS. Further examples of suitable inorganic materials include garnets, sulfides, phosphates, perovskites, antiperovskites, other ion-conducting inorganic materials and / or mixtures thereof. When LixMPySz particles are employed in the ion-conducting layer, they may be formed, for example, using the raw material components Li2S, SiS2, and P2S5 (or alternatively Li2S, Si, S, and P2S5).

[0143] In some embodiments, the ion-conducting layers described herein comprise oxides, nitrides, and / or oxynitrides of lithium, aluminum, silicon, zinc, tin, vanadium, zirconium, magnesium, and / or indium, and / or alloys thereof. Non-limiting examples of suitable oxides include Li2O, LiO, LiO2, LiRO2 where R is a rare earth metal (e.g., lithium lanthanum oxide), lithium titanium oxide, Al2O3, ZrO2, SiO2, CeO2, and Al2TiO5. Further examples of suitable materials that may be employed include lithium nitrate (e.g., LiNO3), lithium silicate, lithium borate (e.g., lithium bis(oxalate)borate, lithium difluoro(oxalate)borate), lithium aluminate, lithium oxalate, lithium phosphate (e.g., LiPO3, Li3PO4), lithium phosphorus oxynitride, lithium silicon sulfide, lithium germanosulfide, lithium fluoride (e.g., LiF, LiBF4, LiAlF4, LiPF6, LiAsF6, LiSbF6, Li2SiF6, LiSO3F, LiN(SO2F)2, LiN(SO2CF3)2), lithium borosulfide, lithium aluminosulfide, lithium phosphosulfide, oxysulfides (e.g., lithium oxysulfide), and / or combinations thereof. In some embodiments, the plurality of particles comprises Li-Al-Ti-PO4 (LATP).

[0144] In some embodiments, the ionically conductive layers described herein include a plurality of particles having a structure indicative of at least partially fused particles and / or particles deposited by aerosol deposition, the plurality of particles comprising an inorganic material. For example, the plurality of particles having a structure indicative of at least partially fused particles and / or particles deposited by aerosol deposition may be formed from an inorganic material. In some embodiments, the plurality of particles having a structure indicative of at least partially fused particles and / or particles deposited by aerosol deposition comprises two or more inorganic materials. The plurality of particles may comprise any suitable material as described above. EXAMPLES

[0145] In the following examples and comparative examples, cells were fabricated in the following manner. The anode was either vacuum-deposited Li (VDLi) (approximately 15-25 μm thick) on 200 nm of Cu as a current collector placed on a polyethylene terephthalate (PET) substrate, or Li foil (2 mil) (1 mil thick / cathode) commercially available from Rockwood Lithium. The VDLi had different degrees of passivation with CO2 and were designated HP VDLi or LP VDLi. The degree of passivation was indicated by the brightness of the lithium appearance measured by a Konica Minolta Color Reader CR-10 Plus 10.01575, L color space. Generally, Li is considered to be heavily passivated and designated HP VDLi when L is less than 40, and Li is considered to be less passivated and designated LP VDLi when L is greater than 60. If the color space of L was within the range of 40 to 60, it was considered to be normal passivated Li and was denoted as VDLi.

[0146] The porous separators used were 25 μm polyolefin (Celgard 2325) or 9 μm polyethylene (Entek EP), and the cathodes used included NCM622, NCM721, or NCM811 coated on 12–20 μm aluminum substrates, with ACM loadings of approximately 19.3–22 mg / cm. 2 The above components were assembled in a three-layer stack of anode / separator / cathode / separator / anode. The total active cathode surface area was 100 cm. 2 After sealing the cell components in a foil pouch, 0.5 mL to 0.55 mL of the appropriate electrolyte was added. The cell package was then vacuum sealed. These cells were immersed in the electrolyte solution unrestrained for 24 to 72 hours and then pressurized at 10 to 12 kg / cm. 2 A pressure of 0.2C (75mA) was applied to the cells. All cells were cycled under such pressure unless otherwise noted. All cells were cycled at a charge voltage of 4.35V cut off at C / 12 (30mA), ramped down to 3mA, and discharged at C / 3 (120mA) for the first three cycles unless otherwise noted. Subsequent charge / discharge cycles were performed under the following conditions: charge at 0.2C (75mA) to 4.35V, then ramped down to 3mA at 4.35V, and discharged at 0.8C (300mA) to 3.2V unless otherwise noted.

[0147] In the following examples and comparative examples, the specific procedure used to measure the discharge capacity of an electrochemical cell during cycling is as follows. First, the cell was connected to a battery cycler channel (such as Maccor, Arbin, or Bitrode) capable of supplying the manufacturer's specified current and voltage. The cell was first discharged at the recommended current (such as C-rate) to the recommended voltage (such as 3.2V) and then rested for 5 minutes. It was then charged at the recommended current (such as C / 4) to the recommended voltage (such as 4.35V), maintained at the recommended voltage (such as 4.35V) until the current decayed to a certain value (such as C / 20), and again rested for 5 minutes. The rest voltage (V1) was measured at the end of this 5-minute rest. The cell was then discharged again at the recommended current (such as C-rate) to the recommended voltage (such as 3.2V). The voltage (V2) was measured 5 minutes after the start of this discharge.

[0148] The discharge capacity C is calculated by the following formula (1): C=I dch t (1) According to the current I dch It can be calculated by multiplying by the time t to reach the discharge voltage cutoff after cycling. The discharge resistance R (for example, the 5-minute discharge resistance) is calculated using the following formula (2): R=(V2-V1) / I dch (2) (Where V1 is the voltage at the end of the pause before discharge, V2 is the voltage measured 5 minutes after the start of discharge, and I dch is the discharge current (A). Cycling continued according to the procedure described above, and the discharge capacity and discharge resistance were calculated for each subsequent cycle. All cells were cycled at room temperature unless otherwise noted.

[0149] (Examples 1 to 5 and Comparative Examples 1 to 5) These examples and comparative examples compare the cycle life of cells including LiF-rich SEI layers formed under the application of pressure to otherwise identical cells without the application of pressure.

[0150] In the following examples and comparative examples, cells were prepared, assembled, and cycled according to the methods described above. Specifically, the anode was vacuum-deposited Li (HP VDLi) (approximately 15-25 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The cathode used had an ACM loading of approximately 19.3-22 mg / cm. 2 The cell was NCM811 coated on an aluminum substrate with a thickness of 12 to 20 μm per surface. The specific components and characteristics of the cell are shown in Table 1.

[0151] Comparative Example 1: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:1.5:1.5 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):ethyl methyl carbonate (EMC). The electrolyte solvent mixture further contained 1 wt. % LiBOB. The cell was not cycled under applied pressure.

[0152] Comparative Example 2: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):methyl acetate (MA). The electrolyte solvent mixture further contained 1 wt.% LiBOB. The cell was not cycled under pressure.

[0153] Comparative Example 3: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):ethyl methyl carbonate (EMC):methyl acetate (MA). The electrolyte solvent mixture further contained 1 wt.% LiBOB. The cell was not cycled under pressure.

[0154] Comparative Example 4: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):ethyl acetate (EA). The electrolyte solvent mixture further contained 1 wt.% LiBOB. The cell was not cycled under pressure.

[0155] Comparative Example 5: The above cell was fabricated with an electrolyte of 1M LiPF6 in a 1:3 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The electrolyte solvent mixture further contained 1 wt% LiBOB. The cell was not cycled under pressure.

[0156] Example 1 The electrochemical cell was identical to the cell of Comparative Example 1, except that the cell of Example 1 was cycled under applied pressure.

[0157] Example 2 The electrochemical cell was identical to the cell of Comparative Example 2, except that the cell of Example 2 was cycled under applied pressure.

[0158] Example 3 The electrochemical cell was identical to the cell of Comparative Example 3, except that the cell of Example 3 was cycled under applied pressure.

[0159] Example 4 The electrochemical cell was identical to the cell of Comparative Example 4, except that the cell of Example 4 was cycled under applied pressure.

[0160] Example 5 The electrochemical cell was identical to the cell of Comparative Example 5, except that the cell of Example 5 was cycled under applied pressure.

[0161] TIFF2024511168000002.tif107159

[0162] Effect of pressure application on cycle life The effect of applied pressure on the cycle life of electrochemical cells containing LiF-rich SEI layers (SEI layers with relatively high loadings of LiF) was investigated. Figures 4-8A show the discharge capacity as a function of cycle number for various electrolyte systems comparing cells with applied pressure (Examples 1-5) and cells without applied pressure (Comparative Examples 1-5). As shown in Table 1, the LiF-rich SEI layer was formed as a result of FEC degradation during cycling for both cells cycled with and without applied pressure. As shown, the cells containing LiF-rich SEI layers formed under applied pressure exhibited longer cycle life (as shown in Figures 4-8A) compared to cells containing LiF-rich SEI layers formed without applied pressure. Additional inorganic materials (e.g., Li2O) associated with electrolyte (e.g., FEC) degradation were also observed in the SEI layers of Examples 1-5.

[0163] As shown in Figures 4 to 8A, in the presence of a passivation agent (e.g., LiBOB), the cycle life of the unpressurized cells (Comparative Examples 1 to 5) was about 20 to 50 cycles, whereas the cycle life of the unpressurized cells was about 12 kg / cm 2 The cycle life of the cells cycled under a pressure of 1000 m / s was more than 250 cycles. Thus, the cells containing a LiF-rich SEI layer formed without the application of pressure were significantly worse than the cells containing a LiF-rich SEI layer formed under the application of pressure. This result suggests that the application of pressure allows in-situ control of the SEI growth during cycling, which results in an extended cell cycle life.

[0164] The formation of resistive SEI, which continues to grow during cycling, was one of the main causes leading to cell failure due to polarization accumulation. To investigate the effect of pressure application on the in-situ formation of resistive SEI during cycling, the discharge resistance (i.e., 5-min discharge resistance) was calculated for Example 5 according to Equation (2) and compared with that of Comparative Example 5. Figure 8B shows the 5-min discharge resistance of the cells with and without pressure normalized to the 5-min discharge resistance at the 5th charge-discharge cycle of each cell. As shown in Figure 8B, the cell with pressure (Example 5) showed a slower increase in 5-min discharge resistance compared to the cell without pressure (Comparative Example 5). This result suggested that pressure application during cycling inhibited the growth of SEI resistance, thus slowing down the polarization accumulation of the cell, and significantly increased the cycling performance from about 20 cycles (Comparative Example 5) to about 250 cycles (Example 5).

[0165] (Example 6 and Comparative Examples 6 to 10) These examples and comparative examples compare the cycle life of a cell that includes a LiF-rich SEI layer with an otherwise identical cell that does not include a LiF-rich SEI layer.

[0166] In the following examples and comparative examples, cells were prepared, assembled, and cycled according to the methods described above. Specifically, the anode was vacuum-deposited Li (HP VDLi) (approximately 15-25 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The cathode used had an ACM loading of approximately 19.3-22 mg / cm. 2 The cell was NCM811 coated on an aluminum substrate with a thickness of 12 to 20 μm per surface. The specific components and characteristics of the cell are shown in Table 2.

[0167] Comparative Example 6 The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 3:7 weight ratio electrolyte solvent mixture of ethylene carbonate (EC):ethyl methyl carbonate (EMC) (BASF LP57).

[0168] Comparative Example 7 The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 3:7 weight ratio electrolyte solvent mixture of ethylene carbonate (EC):diethyl carbonate (DEC) (BASF LP47).

[0169] Comparative Example 8 The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:1 weight ratio electrolyte solvent mixture (BASF LP50) of ethylene carbonate (EC):ethyl methyl carbonate (EMC).

[0170] Comparative Example 9 The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:1 weight ratio electrolyte solvent mixture of ethylene carbonate (EC):diethyl carbonate (DEC) (BASF LP40).

[0171] Comparative Example 10 The above cell was fabricated using an electrolyte containing 1M LiPF6 in an electrolyte solvent mixture (BASF LP30) with a weight ratio of 1:1 ethylene carbonate (EC): dimethyl carbonate (DMC).

[0172] Example 6 A cell as above was constructed using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC).

[0173] TIFF2024511168000003.tif73152

[0174] As shown in FIG. 9, the cells containing EC-based electrolytes (Comparative Examples 6-10) exhibited a lifespan of about 30-110 cycles (80% of rated capacity) even under the pressure applied during cycling, which was significantly lower than the cells using FEC as a co-solvent (Example 6). As shown, the cells containing FEC as a co-solvent in the electrolyte mixture exhibited a cycle lifespan of about 190 cycles and showed the formation of a LiF-rich SEI layer (an SEI layer containing a relatively high loading of LiF) that was not formed in the cells of Comparative Examples 6-10 (Table 1). This result indicated that the formation of an inorganic-rich SEI layer (e.g., LiF) is important for improving the cycle life of Li metal cells. It should be noted that LP30, LP40, LP50, LP47, and LP57 are standard electrolytes commonly used in Li-ion batteries.

[0175] (Example 7 and Comparative Examples 11 to 15) These examples and comparative examples compare the individual effects of pressure application, additives, cathode type, and fluorinated electrolyte solvents (eg, FEC) on the cycle life of electrochemical cells.

[0176] In the following examples and comparative examples, cells were prepared, assembled, and cycled as described above. Specifically, the anode was vacuum evaporated Li (HP VDLi or LP VDLi) (approximately 15-25 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The cathode used was a 12-20 μm aluminum substrate with an ACM loading of approximately 19.3-22 mg / cm. 2 The specific components and properties of the cell are shown in Table 3.

[0177] Comparative Example 11: The above cell was fabricated using an electrolyte of 1M LiPF6 in a 1:1 weight ratio electrolyte solvent mixture of ethylene carbonate (EC):dimethyl carbonate (DMC) (BASF LP30). The cell was not cycled under applied pressure.

[0178] Comparative Example 12: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). This cell was not cycled under applied pressure.

[0179] Comparative Example 13: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The electrolyte solvent mixture further contained 1 wt% LiBOB. The cell was not cycled under pressure.

[0180] Comparative Example 14: The above cell was constructed using an electrolyte of 1M LiPF6 in a 1:1 weight ratio electrolyte solvent mixture of ethylene carbonate (EC):dimethyl carbonate (DMC) (BASF LP30), and cycled under applied pressure.

[0181] Comparative Example 15: The above cell was fabricated using an electrolyte of 1M LiPF6 in a 1:10:10 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):ethylene carbonate (EC):dimethyl carbonate (DMC) (BASF LP30 with 4 wt% FEC) and cycled under pressure.

[0182] Example 7 The above cell was constructed with an electrolyte of 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC), and cycled under applied pressure.

[0183] TIFF2024511168000004.tif74160

[0184] As shown in Figure 10, cells cycled without applied pressure (Comparative Examples 11-13) had limited cycle life, even in the presence of a LiF-rich SEI and in the presence of LiBOB additive. This poor cycling performance due to the lack of applied pressure in Li metal cells was observed regardless of the cell's cathode type, e.g., NCM622 in Comparative Examples 11-13 or NCM811 in Comparative Examples 1-5.

[0185] Furthermore, as shown in Figure 11, the cell containing 4% FEC in the electrolyte (Comparative Example 15) showed slightly improved cycling performance compared to the cell without FEC in the electrolyte (Comparative Example 14), but still significantly below the cell with a higher loading of FEC (Example 7) which resulted in the formation of a LiF-rich SEI layer according to Table 3. Furthermore, Figure 11 shows that for the cell with cathode NCM622 and Li metal (LP VDLI), the combination of a LiF-rich SEI layer and pressure application resulted in improved cycle life of the electrochemical cell due to slowing down the polarization accumulated during cell cycling.

[0186] (Examples 8 to 16) These examples compare the cycle life of a cell containing an SEI layer rich in LiF and Li2CO3 to an otherwise identical cell containing an SEI layer rich only in LiF.

[0187] In the following examples and comparative examples, cells were prepared, assembled, and cycled as described above. Specifically, the anode used was a Li foil (2 mil) available from Rockwood Lithium (thickness 1 mil / cathode). The cathode used had an ACM loading of about 19.3-22 mg / cm. 2 The cell was NCM811 coated on an aluminum substrate with a thickness of 12 to 20 μm per surface. The specific components and characteristics of the cell are shown in Table 4.

[0188] Example 8 The above cell was fabricated using an electrolyte of 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of this cell was 4.35V.

[0189] Example 9: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of this cell was 4.6V.

[0190] Example 10: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of this cell was 4.7V.

[0191] Example 11: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of the cell was 4.4 V. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0192] Example 12: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:4 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of the cell was 4.6 V. The electrolyte solvent mixture further contained 1 wt. % LiBOB.

[0193] Example 13: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:3 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of this cell was 4.35V.

[0194] Example 14 The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:3 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of this cell was 4.6V.

[0195] Example 15: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:3 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of the cell was 4.4 V. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0196] Example 16: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:3 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The formation voltage of the cell was 4.7 V. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0197] TIFF2024511168000005.tif99155

[0198] In Examples 8-10, the effect of increasing the formation voltage was investigated. As shown in Table 4, increasing the formation voltage resulted in the formation of a Li2CO3-rich inorganic SEI layer in addition to LiF (Examples 9-10). The LiF and Li2CO3-rich SEI layer contained relatively high loadings of LiF and Li2CO3. Furthermore, as shown in FIG. 12A, a higher formation voltage further resulted in an increase in cell cycling performance beyond 350 cycles (Example 10). A similar increase in cell cycling performance at higher formation voltage was observed in cells with electrolytes with higher FEC content (Examples 13-14, as shown in FIG. 14).

[0199] The effect of high formation voltage on the in-situ formation of resistive SEI during cycling was investigated and is shown in FIG. 12B. The discharge resistance (i.e., 5 min discharge resistance) was calculated for Examples 8-10. FIG. 12B plots the 5 min discharge resistance of the cells normalized against the 5 min discharge resistance at the 5th cycle of each cell. As shown, the cell with high formation voltage (Example 10) showed a slower increase in 5 min discharge resistance during cycling compared to the cell with low formation voltage (Example 8). This suggests that the application of high formation voltage affected the in-situ formation of the SEI layer and suppressed the growth of SEI resistance. As a result, as shown in FIG. 12A, the cycling performance of the cell with 4.7 V formation (Example 10) was improved over 100 cycles compared to the cell with normal 4.35 V formation (Example 8).

[0200] The effect of an additive (LiBOB) in addition to high formation voltage was investigated and is shown in Figure 13. As shown, cycling performance at high voltage (4.6V) with LiBOB further improved cycle life up to 350 cycles (Example 12). A similar increase in cell cycling performance with LiBOB at higher formation voltage was observed in cells using electrolytes with higher FEC content (Examples 15-16 as shown in Figure 15).

[0201] These examples demonstrate that in-situ Li passivation with CO2 generated at higher formation voltages (e.g., 4.4, 4.6, and 4.7 V) increased the inorganic content of the SEI layer. Such high inorganic content (LiF and Li2CO3) in the SEI layer, resulting from FEC and higher formation voltages, along with in-situ control of SEI growth by pressure application, significantly suppressed the cell impedance build-up and significantly improved cycling performance.

[0202] (Examples 17 to 20) These examples show the cycle life of cells containing acetate-based electrolyte co-solvents at various temperatures (eg, 0° C., room temperature (RT)) and various formation voltages.

[0203] In the following examples and comparative examples, cells were prepared, assembled, and cycled as described above. Specifically, the cathode was vacuum evaporated Li (HP VDLi) (approximately 15-25 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The anode used NCM811 coated on a 12-20 μm aluminum substrate with an ACM loading of approximately 19.3-22 mg / cm. 2 The specific components and characteristics of the cell are shown in Table 5.

[0204] Example 17: The above cell was fabricated using an electrolyte of 1M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):methyl acetate (MA). The formation voltage of this cell was 4.35 V and it was cycled at room temperature.

[0205] Example 18: The above cell was fabricated using an electrolyte of 1 M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):methyl acetate (MA). The formation voltage of this cell was 4.6 V and it was cycled at room temperature.

[0206] Example 19: The above cell was fabricated using an electrolyte of 1 M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):methyl acetate (MA). The formation voltage of the cell was 4.35 V and cycled at 0°C.

[0207] Example 20: The above cell was fabricated using an electrolyte containing 1 M LiPF6 in a 1:2:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC):methyl acetate (MA). The formation voltage of the cell was 4.6 V and cycled at 0°C.

[0208] TIFF2024511168000006.tif56162

[0209] The effect of higher formation voltage on cycle life was investigated in Examples 17-18 and shown in FIG. 16. As shown, higher formation voltage at 4.6 V (Example 18) resulted in increased cycle life for cells containing LiF and Li2CO3-rich SEI layers and cycled at room temperature with methyl acetate (MA) as a co-solvent. A similar positive effect (e.g., increased cycle life) was shown for higher formation voltage at 4.6 V in cells containing LiF and Li2CO3-rich SEI layers and cycled at 0° C. with MA as a co-solvent (Examples 19-20 in FIG. 17).

[0210] (Examples 21 to 22 and Comparative Examples 16 to 17) These examples compare the cycle life of cells containing LiFSI and LiF-rich SEI layers cycled with and without applied pressure, all other factors being equal.

[0211] In the following examples and comparative examples, cells were prepared, assembled, and cycled as described above. Specifically, the anode was vacuum evaporated Li (HP VDLi) (approximately 15-25 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The cathode used had an ACM loading of approximately 19.3-22 mg / cm. 2 The cell was NCM811 coated on an aluminum substrate with a thickness of 12 to 20 μm per surface. The specific components and characteristics of the cell are shown in Table 6.

[0212] Comparative Example 16: The above cell was fabricated using an electrolyte containing 0.8M LiFSI in a 1:4 by weight electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The cell was not cycled under pressure. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0213] Comparative Example 17: The above cell was fabricated using an electrolyte containing 0.8M LiFSI in a 1:3 by weight electrolyte solvent mixture of fluoroethylene carbonate (FEC):ethyl methyl carbonate (EMC). The cell was not cycled under pressure. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0214] Example 21 The electrochemical cell was identical to the cell of Comparative Example 16, except that the cell of Example 21 was cycled under pressure.

[0215] Example 22 The electrochemical cell was identical to the cell of Comparative Example 17, except that the cell of Example 22 was cycled under pressure.

[0216] TIFF2024511168000007.tif56150

[0217] These examples demonstrated that in lithium bis(fluorosulfonyl)imide (LiFSI)-based electrolytes, an inorganic (e.g., LiF)-rich SEI layer produced by FEC solvent and the application of pressure resulted in improved cycling performance (e.g., Examples 21 and 22 shown in Figures 18-19). This trend was consistent with previous examples (Examples 1-20) that used LiPF6 as the salt.

[0218] As shown in Figures 18-19, the SEI layers in each of the examples and comparative examples showed the formation of inorganic compounds (e.g., LiF-rich) due to the presence of FEC. However, the cells without applied pressure generally survived less than 20 cycles and the cells with applied pressure of 12 kg / cm for more than 250 cycles. 2 This was significantly lower than that of the cells cycled under a pressure of 1000 kPa (Examples 21-22). This result suggested that the in-situ control of SEI growth by pressure is important in LiFSI-based electrolytes.

[0219] Furthermore, promising results were observed when these LiFSIs were used in cells. LiFSI, a salt known to cause Al corrosion, is typically used as a co-salt with LiPF6, an Al corrosion inhibitor, to prevent Al corrosion. However, as shown by the results of Examples 21-22, Al corrosion was suppressed even when LiFSI was used as a single salt. The use of LiFSI as a single salt in electrochemical cells may be advantageous for high temperature applications due to its high thermal stability.

[0220] (Example 23) This example illustrates the physical properties of an SEI layer formed in an electrochemical cell.

[0221] The cells were prepared, assembled, and cycled as previously described. Specifically, the anode used was Li foil (2 mil) commercially available from Rockwood Lithium (thickness 1 mil / cathode). The porous separator used was 25 μm polyolefin (Celgard 2325) and the cathode used had an ACM loading of approximately 19.3-22 mg / cm. 2 NCM622 coated on aluminum substrate with thickness of 12-20μm / surface The above components were assembled into a three-layer stack of anode / separator / cathode / separator / anode. The cells were fabricated with an electrolyte containing 1M LiPF6 in an electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC) in a 1:4 weight ratio. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0222] For the first three formation cycles, the cell was charged to 4.35 V at 30 mA, ramped down to 10 mA, and discharged at 120 mA. Subsequent charge and discharge cycles were performed under the following conditions: charge to 4.35 V at 200 mA, ramped down to 10 mA, then discharged with 1 second pulses at 800 mA, with a 3 second pause between each pulse, until the voltage reached 3.2 V. The cutoff was 60% of the rated capacity. The cell was cycled under pressure.

[0223] SEM / EDS characterization of the SEI was performed (FIGS. 20A-B). The cycled anode was retrieved from the expired cell (after 123 charge and discharge cycles), rinsed with dimethyl carbonate, and analyzed by SEM / EDS. As shown, FIGS. 20A-B show the presence of an SEI layer that includes two regions with different atomic content, a first region of the SEI layer adjacent to the separator and a second region of the SEI layer adjacent to the anode, where the first region of the SEI layer adjacent to the separator is rich in fluorine atoms. Additionally, FIG. 20C shows that the portion of the SEI layer adjacent to the separator includes nano-sized particles.

[0224] Example 24 This example shows the chemical composition of the SEI layer formed in an electrochemical cell.

[0225] The cells were prepared, assembled, and cycled according to the methods previously described. Specifically, the anode was vacuum deposited Li (HP VDLi) (approximately 20 μm thick) deposited on 200 nm of Cu as a current collector deposited on a polyethylene terephthalate (PET) substrate. The porous separator used was 9 μm polyethylene (Entek EP) and the cathode used had an ACM loading of approximately 19.3-22 mg / cm. 2 The materials used were NCM721 coated on aluminum substrates with a thickness of 12-20 μm per side. The above components were assembled into a stacked tri-layer structure of anode / separator / cathode / separator / anode. The cells were fabricated with an electrolyte containing 1 M LiPF6 in an electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC) in a 1:4 weight ratio. The electrolyte solvent mixture further contained 1 wt% LiBOB.

[0226] For the first three formation cycles, the cell was charged at 30 mA to 4.4 V, ramped down to 10 mA, and discharged at 120 mA. Subsequent charge and discharge cycles were performed under the following conditions: charge at 75 mA to 4.4 V, ramped down to 10 mA, then charge at 300 mA to 3.2 V. The cell was cycled under pressure.

[0227] SEM / EDS was performed on a cross-section of the SEI layer / separator interface (Figure 21). The specimen was prepared by sputter coating an ultrathin conductive palladium layer onto the cross-section. The composition of the SEI layer was shown by EDS line scan of the ion milled cross-section (line width 0.1 μm at 5 KV). As shown by the EDS line scan, the region of the SEI layer adjacent to the separator was fluorine rich.

[0228] The chemical composition of fluorine in the SEI layer is shown in Figure 22 A. As shown, at least 70% of the total fluorine content in the SEI layer comes from LiF.

[0229] The chemical composition of lithium in the SEI layer is shown in Figure 22B. As shown, in addition to LiF, other inorganic materials (e.g., Li2O) were also present in the SEI layer.

[0230] The chemical composition of carbon in the SEI layer is shown in Figure 22 C. Other carbon-containing species such as alkyl carbonates (ROCO2Li) and possibly alkoxides (ROLi) and polyethers (-CH2O-) were also present in the SEI layer.

[0231] The crystallinity of the SEI layer was measured and is shown in Figure 23. As shown, the XRD results showed the presence of crystalline LiF and Li2O in the SEI layer.

[0232] (Examples 25 to 26 and Comparative Examples 18 to 19) This example compares the cycle life of a cell containing an SEI layer formed under pressure to a cell containing an SEI layer formed without under pressure, all other factors being equal.

[0233] In the following examples and comparative examples, cells were fabricated and assembled by the methods described above. Specifically, the anode was vacuum deposited Li (HP VDLi) (approximately 15-25 μm thick). The cathode used was NCM811. The porous separator used was a 9 μm polyethylene (Entek EP) separator. The above components were assembled into a laminated tri-layer structure of anode / separator / cathode / separator / anode. The cell components were sealed in a foil pouch before electrolyte was added. The cell package was then vacuum sealed. These cells were immersed in the electrolyte solution unrestrained for 24-72 hours and then loaded with 12 kg / cm2 of electrolyte. 2 A pressure of 0.2C (75mA) was applied to the cells. All cells were cycled under these pressures unless otherwise noted. The cell capacity of each cell was 370mAh. All cells were cycled at a charge voltage of 4.35V cut off at C / 12 (30mA), ramped down to 10mA, and discharged at a C / 3 (120mA) rate for the first three formation cycles unless otherwise noted. Subsequent charge and discharge cycles were performed under the following conditions: charge at 0.2C (75mA) to 4.35V, ramped down to 10mA, and discharged at 0.8C (300mA) to 3.2V unless otherwise noted.

[0234] Comparative Example 18: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:1 electrolyte solvent mixture by weight of ethylene carbonate (EC):dimethyl carbonate (DMC). The cell was not cycled under pressure. The formation voltage of the cell was 4.35V.

[0235] Comparative Example 19: The above cell was fabricated using an electrolyte containing 1M LiPF6 in a 1:1 weight ratio electrolyte solvent mixture of fluoroethylene carbonate (FEC):dimethyl carbonate (DMC). The cell was not cycled under pressure. The formation voltage of the cell was 4.35V.

[0236] (Example 25) The electrochemical cell was prepared by subjecting the cell of Example 25 to a load of 12 kg / cm2 The cell was identical to that of Comparative Example 18, except that it was cycled at a pressure of 1.5 V. The formation voltage of the cell was 4.35 V.

[0237] (Example 26) The electrochemical cell was prepared by subjecting the cell of Example 26 to a load of 12 kg / cm 2 The cell was identical to that of Comparative Example 19, except that it was cycled at a pressure of 1.5 V. The formation voltage of the cell was 4.35 V.

[0238] FIG. 24 shows the cycling performance of electrochemical cells cycled under pressure (Examples 25 and 26) and cells cycled without pressure (Comparative Examples 18 and 19). For each Example and Comparative Example shown in FIG. 24, two identical cells were tested (n=2). As shown in FIG. 24, the cells cycled under pressure (Examples 25 and 26) exhibited significantly longer cycle life than the cells cycled without pressure (Comparative Examples 18 and 19). The cell without fluorinated solvent (Comparative Example 18) had a poorer cycle life when cycled without pressure. Furthermore, even when pressure was applied during cycling, the cell without fluorinated solvent (Example 25) performed worse (i.e., had a shorter cycle life) than the cell containing fluorinated solvent and all other factors being equal (Example 26). The longest cycle life was observed for the cell containing fluorinated solvent and cycled under pressure (Example 26).

[0239] XRD, SEM, and EDS measurements were performed on cross sections of the separator interface / SEI layer / anode interface. After the 25th discharge, each sample was opened and a section containing the Li anode with SEI was retrieved. Ion milled cross sections were obtained for each example. The composition of the SEI layer was shown by EDS line scans of the ion milled cross sections. Figures 25-28 are SEM / EDS line scans of electrochemical cells from Comparative Example 18, Example 25, Comparative Example 19, and Example 26, respectively.

[0240] As shown by the EDS line scan in FIG. 25, in the electrochemical cell containing a non-fluorinated solvent and cycled without pressure (Comparative Example 18), the SEI layer in the cell was oxygen-rich throughout the entire thickness of the SEI. Similarly, as shown by the EDS line scan in FIG. 26, in the electrochemical cell containing a non-fluorinated solvent and cycled with pressure (Example 25), the SEI layer in the cell remained oxygen-rich throughout the entire thickness of the SEI. Also, as shown in FIG. 27, in the electrochemical cell containing a fluorinated solvent and cycled without pressure (Comparative Example 19), the SEI layer in the cell was oxygen-rich throughout the entire thickness of the SEI. However, as shown in FIG. 28, in the electrochemical cell containing a fluorinated solvent and cycled with pressure (Example 26), the region of the SEI layer adjacent to the separator was fluorine-rich.

[0241] XDR was performed to measure the crystallinity and composition of the various SEI layers in the samples of Examples 25-26 and Comparative Examples 18-19. As shown in Table 7, nanocrystalline LiF was observed in the samples with FEC-containing electrolyte (Comparative Example 19 and Example 26) regardless of whether the samples were cycled under pressure. Furthermore, the electrolyte in the samples from Comparative Example 19 and Example 26 induced the formation of an inorganic-rich SEI containing both nanocrystalline LiF and Li2O. Furthermore, the cell cycled under pressure (Example 26) exhibited a LiF / Li2O ratio of 0.2, lower than the LiF / Li2O ratio of 2.1 for the cell cycled without pressure (Comparative Example 19). As shown in Table 7 and FIG. 24, the cycling performance could be improved by controlling the presence of various SEI components, for example, by applying pressure to achieve a favorable LiF / Li2O ratio. The presence of other inorganic species detected in the SEI layer is shown in Table 7.

[0242] TIFF2024511168000008.tif77144

[0243] The increase in SEI resistivity (or polarization) and Li protection capability were measured for various cells of Examples 25-56 and Comparative Examples 18-19 utilizing the C-rate Li-stripping technique (e.g., as shown in FIG. 29). The Li-stripping technique was performed as follows: cells at the 25th discharge (Q25), 100th discharge (Q100), and 75% cut-off capacity (EOL) were discharged to 0 V at 300 mA, 50 mA, 25 mA, 10 mA, 5 mA, and 2 mA, respectively. The realized capacity was converted to lithium thickness based on the theoretical capacity (3862 mAh / g) and density (0.534 g / cc). SEI thickness and density were measured at Q25 and Q100 to evaluate the physical properties and growth of the SEI layer, as shown in Tables 8 and 9. Notably, the cells without applied pressure (Comparative Examples 18 and 19) reached EOL before 25 cycles. The weight of the SEI layer was calculated based on the difference between the cycled anode weight and the residual metallic Li of sister cells measured by Li stripping.

[0244] FIG. 29 shows the percentage of residual Li for the cell without fluorinated solvent and cycled under pressure (Example 25) versus the cell with fluorinated solvent and cycled under pressure (Example 26). The percentage of residual Li at C-rate is equal to (Li removed at C-rate) / (total Li removed at all rates). The percentage of Li removed at C-rate could be used to indicate the resistivity of the SEI. A higher percentage of Li removed (corresponding to a lower percentage of residual Li) correlates with a less polarized cell, indicating a less resistive SEI. As shown in FIG. 29, the SEI resistivity of the cell with fluorinated solvent (Example 26) increased at a slower rate over the course of cycle life compared to the SEI resistivity of the cell without fluorinated solvent (Example 25). The cell with fluorine-rich SEI (Example 26) showed a decrease in polarization.

[0245] As shown in Tables 8 and 9, the effect of pressure application on the thickness and density of the resulting SEI layer was observed to be different for the cell with fluorinated electrolyte solvent (Example 26) and the cell without fluorinated electrolyte solvent (Example 25). Under pressure application, a significant decrease in the increase in thickness and bulk density was observed for the cell without fluorinated electrolyte solvent (Example 25), while no substantial change in thickness and bulk density was observed for the cell with fluorinated electrolyte solvent (Example 26). This result indicates that a combination of fluorinated solvent and pressure application during cycling can be used to tune the SEI chemical composition and improve cycling performance, which is consistent with the XRD results shown in Table 7. Furthermore, a slower increase in SEI thickness and decrease in SEI bulk density was observed with the combination of fluorinated electrolyte solvent and pressure application compared to the cell without fluorinated electrolyte solvent (Example 25).

[0246] TIFF2024511168000009.tif58136

[0247] TIFF2024511168000010.tif57138

[0248] FIG. 30 shows the discharge capacity as a function of cycle number for cells cycled under pressure with and without fluorinated solvents (Examples 25 and 26). Table 10 shows the effect of lithium stripping on the cells of FIG. 30. For each of Examples 25 and 26, two identical cells were tested (n=2). As shown by the significantly higher amount of lithium stripped at C-rate in Table 10, the cell with a fluorine-rich SEI layer (Example 26) was more conductive than the cell without a fluorine-rich SEI layer (Example 25). Furthermore, the cell with a fluorine-rich SEI layer (Example 26) had better protection capability and therefore less lithium loss per cycle number and per stored capacity.

[0249] TIFF2024511168000011.tif58155

[0250] While several embodiments of the invention have been described and illustrated herein, those skilled in the art will readily envision various other means and / or structures for performing the functions and / or results and / or obtaining one or more of the advantages set forth above, and each such variation and / or improvement is deemed to be within the scope of the present invention. More generally, those skilled in the art will readily appreciate that all parameters, dimensions, materials, and configurations described herein are meant to be exemplary, and that the actual parameters, dimensions, materials, and / or configurations will depend on the particular application for which the teachings of the present invention are used. Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to certain aspects of the invention described herein. Thus, the foregoing aspects are presented by way of example only, and it should be understood that within the scope of the appended claims and equivalents thereof, the invention may be practiced otherwise than as specifically described and claimed. The present invention relates to each individual feature, system, article, material, kit, and / or method described herein. Also, combinations of two or more such features, systems, articles, materials, kits, and / or methods are encompassed within the scope of the invention, if such features, systems, articles, materials, kits, and / or methods are not mutually inconsistent.

[0251] All definitions should be understood to control for any dictionary definitions, definitions in documents incorporated by reference, and / or ordinary meaning of the defined terms as defined and used herein.

[0252] As used in the specification and the claims, the indefinite articles "a" and "an" should be understood to mean "at least one," unless expressly indicated otherwise.

[0253] As used in the specification and claims, the phrase "and / or" should be understood to mean "either or both" of conjugated elements, i.e., elements that are present conjunctively in some cases and disjointly in others. Unless expressly indicated, other elements may optionally be present other than the elements specifically identified by the "and / or" clause, whether related or unrelated to those elements specifically identified. Thus, as a non-limiting example, "A and / or B," when used in conjunction with an open-ended term such as "comprising," means, in one embodiment, A without B (optionally including elements other than B); in another embodiment, B without A (optionally including elements other than A); in yet another embodiment, both A and B (optionally including other elements); and so forth.

[0254] As used in the specification and claims, "or" should be understood to have the same meaning as "and / or" as defined above. For example, when separating items in a list, "or" or "and / or" is inclusive, i.e., It should be construed to include at least one, including more than one, of a number or list of elements, and optionally further items not listed. Only the items explicitly indicated, e.g., "only one of" or "exactly one of," or "comprising" when used in the claims, means including exactly one of a number or list of elements. In general, the term "or" as used herein will only be construed as indicating exclusive alternatives (i.e., "one or the other but not both") when preceded by a term of exclusivity, such as "either," "one of," "only one of," or "exactly one of." When used in the claims, "essentially comprising" has its ordinary meaning as used in the field of patent law.

[0255] As used in the specification and claims, the phrase "at least one" in reference to a list of one or more elements should be understood to mean at least one element selected from one or more elements in the list of elements, but not necessarily including at least one of each element specifically listed in the list of elements, and not necessarily excluding combinations of elements in the list of elements. This definition also allows for elements to be optionally present other than elements specifically identified in the list of elements, meaning related or unrelated to those elements specifically identified. Thus, as a non-limiting example, "at least one of A and B" (equivalently, "at least one of A or B," or, equivalently, "at least one of A and / or B") can mean, in one embodiment, at least one, including optionally more than one, A (optionally including elements other than B) in the absence of B; in another embodiment, at least one, including optionally more than one, B (optionally including elements other than A) in the absence of A; in yet another embodiment, at least one, including optionally more than one, A and at least one, including optionally more than one, B (optionally including other elements); etc.

[0256] Additionally, unless expressly indicated to the contrary, in any method described herein that includes multiple steps or acts, the order of the steps or acts of the method should not be construed as necessarily limited to the order of the steps or acts.

[0257] Throughout the claims as well as in the specification, all transitional phrases such as "comprising," "including," "carrying," "having," "containing," "involving," "holding," and the like, are intended to be open-ended, i.e., to mean including, but not limited to, the following. Only the transitional phrases "including" and "consisting essentially of" are closed or semi-closed transitional phrases, respectively, as set forth in the United States Patent Office Manual of Patent Examining Procedures, Section 2111.03. [Explanation of symbols]

[0258] 10, 100 … electrochemical cells 12 ... Anode 14 … electrolyte 16 ... Cathode 18, 118 … solid electrolyte interfacial layer 20 … Cathode current collector 22 ... Anode current collector 24 … Anode surface

Claims

1. an anode comprising lithium metal, a lithium alloy, or a combination thereof as an anode active material; an electrolyte comprising a fluorinated organic solvent; Cathode, and A solid electrolyte interfacial layer disposed between the anode and the electrolyte. Equipped with The solid electrolyte interface layer is made of LiF and Li 2 CO 3 The inorganic material includes An electrochemical cell, wherein a first ratio of fluorine atoms to oxygen atoms adjacent the electrolyte is higher than a second ratio of fluorine atoms to oxygen atoms adjacent the anode in the solid electrolyte interface layer.

2. an anode comprising lithium metal, a lithium alloy, or a combination thereof as an anode active material; an electrolyte comprising a fluorinated organic solvent; Cathode, and A solid electrolyte interfacial layer disposed between the anode and the electrolyte. Equipped with the solid electrolyte interfacial layer comprises LiF; and (1) a hardness of 0.001 GPa or more and 5 GPa or less, and / or (2) Porosity of 1% or more and 90% or less having An electrochemical cell, the electrochemical cell exhibiting a decrease in discharge capacity of 10% or less after 100 charge / discharge cycles relative to the discharge capacity at the 5th charge / discharge cycle after formation.

3. an anode comprising lithium metal, a lithium alloy, or a combination thereof as an anode active material and having a surface; Cathode, and an electrolyte comprising a fluorinated organic solvent disposed between the anode and the cathode; Equipped with applying an anisotropic force to the surface of the anode; applying a formation voltage during at least one period during charging and / or discharging of the cell; and forming a solid electrolyte interfacial layer adjacent said surface of said anode. [0023] The formation voltage is greater than 4.35 V; The solid electrolyte interface layer is made of LiF and Li 2 CO 3 A method for storing and using electrical energy comprising an inorganic material comprising:

4. 3. The electrochemical cell of claim 1 or 2, wherein the LiF is present in the solid electrolyte interfacial layer in an amount of at least 10% by weight.

5. The solid electrolyte interface layer has a Li amount of at least 10 wt. % in the solid electrolyte interface layer. 2 3. The electrochemical cell of claim 1 or 2, further comprising O.

6. 3. The electrochemical cell of claim 1, further comprising a separator disposed between the anode and the cathode, the separator including pores through which an electrolyte can reside.

7. 3. The electrochemical cell of claim 1 or 2, wherein the solid electrolyte interfacial layer adjacent the separator comprises particles having a size of 10 nm or more and 200 nm or less.

8. LiF and Li 2 CO 3 2. The electrochemical cell of claim 1 , wherein the in situ formation of the solid electrolyte interfacial layer comprising:

9. 9. The electrochemical cell of claim 8, wherein the formation voltage is greater than 4.35V and less than or equal to 4.9V.

10. The Li 2 CO 3 However, CO 2 10. The electrochemical cell of claim 1 formed by the reaction of a cation exchange salt with lithium metal.

11. The solid electrolyte interfacial layer is a mixture of LiF and Li 2 CO 3 3. The electrochemical cell of claim 1 or 2, comprising:

12. 3. The electrochemical cell of claim 1 or 2, wherein the LiF is present in the solid electrolyte interfacial layer in an amount of at least 10% by weight.

13. The Li 2 CO 3 3. The electrochemical cell of claim 1 or 2, wherein is present in the solid electrolyte interfacial layer in an amount of at least 10% by weight.

14. 3. The electrochemical cell of claim 1 or 2, wherein the solid electrolyte interfacial layer further comprises one or more of lithium alkoxides, lithium oxides, lithium salts, and decomposition products of an electrolyte.

15. 3. The electrochemical cell of claim 1 or 2, wherein the electrolyte comprises at least one fluorinated organic solvent selected from cyclic and linear fluorinated carbonates, fluorinated ethers, and fluorinated esters.

16. 3. An electrochemical cell according to claim 1 or 2, wherein the electrolyte comprises at least one fluorinated organic solvent selected from fluoroethylene carbonate and / or difluoroethylene carbonate.

17. 3. The electrochemical cell of claim 1 or 2, wherein the electrolyte comprises at least one non-fluorinated organic solvent, the at least one non-fluorinated organic solvent comprising an ester-based solvent.

18. 3. The electrochemical cell of claim 1 or 2, wherein the fluorinated organic solvent is present in an amount of from 14% to 88% by weight of the total electrolyte weight.

19. The electrochemical cell of claim 1 or 2, wherein the electrolyte further comprises at least one passivator, the passivator comprising an oxalate salt.

20. 3. The electrochemical cell of claim 1 or 2, wherein the cathode is a lithium-intercalation cathode.

21. 3. The electrochemical cell of claim 1 or 2, wherein a first ratio of fluorine atoms to oxygen atoms adjacent the electrolyte is higher in the solid electrolyte interface layer than a second ratio of fluorine atoms to oxygen atoms adjacent the anode based on an average ratio of fluorine atoms to oxygen atoms across a thickness of the solid electrolyte interface layer.

22. The solid electrolyte interface layer is made of LiF and Li in a weight ratio of 1:5 or more and 2:1 or less. 2 3. The electrochemical cell of claim 1 or 2, comprising O.

23. 3. The electrochemical cell of claim 1 or 2, wherein the solid electrolyte interfacial layer has a thickness of 10 nm to 75 μm.